Optical laminate, laminated optical film, optical article, virtual reality display device
Patent Information
- Application Number
- CN202280041188.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-01-19
- Filing Date
- 2022-06-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-06-09
AI Technical Summary
[0076]本发明能够提供一种在虚拟现实显示装置或电子取景器等中使用时重影的产生较少的能够用于反射圆偏振器的光学用层叠体。
Smart Images

Figure CN117460976B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an optical laminate, a laminated optical film, an optical article, and a virtual reality display device. Background Technology
[0002] A reflective polarizer is a polarizer that reflects one polarized light from an incident beam and transmits another polarized light. Based on the reflective polarizer, the reflected and transmitted light are in mutually orthogonal polarization states. Here, mutually orthogonal polarization states refer to polarization states that are located at antipodal points on a Bonga sphere; for example, mutually orthogonal linearly polarized light, right-handed circularly polarized light, and left-handed circularly polarized light correspond to this.
[0003] As reflective linear polarizers that convert transmitted and reflected light into linearly polarized light, examples include thin films formed by stretching dielectric multilayer films as described in Patent Document 1 and metal wire grid polarizers as described in Patent Document 2.
[0004] Furthermore, as a reflective circular polarizer that converts transmitted and reflected light into circularly polarized light, for example, there are known thin films having a light-reflecting layer formed by immobilizing a cholesterol-type liquid crystal phase, as described in Patent Document 3.
[0005] A reflective polarizer is used to extract only specific polarized light from incident light, separating the incident light into two polarized beams. For example, in a liquid crystal display device, it reflects and reuses unwanted polarized light from a backlight, thereby serving as a brightness enhancement film to improve light utilization efficiency. Furthermore, in a liquid crystal projector, it can also be used as a beam splitter to separate light from a light source into two linearly polarized beams and supply them separately to the liquid crystal panel.
[0006] Furthermore, in recent years, methods using reflective polarizers have been proposed for generating virtual and real images by reflecting external light and a portion of the light from an image display device. For example, Patent Document 4 discloses a rearview mirror for vehicles that uses a reflective polarizer to reflect light from behind. Moreover, Patent Document 5 discloses a method for generating virtual images by reflecting light back and forth between a reflective polarizer and a semi-reflective mirror in order to miniaturize and thin the display unit in virtual reality display devices and electronic viewfinders.
[0007] Previous technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2011-053705
[0010] Patent Document 2: Japanese Patent Application Publication No. 2015-028656
[0011] Patent Document 3: Japanese Patent No. 6277088
[0012] Patent Document 4: Japanese Patent Application Publication No. 2017-227720
[0013] Patent Document 5: Japanese Patent Application Publication No. 7-120679 Summary of the Invention
[0014] The technical problem to be solved by the invention
[0015] According to the inventors' research, it has been found that when a portion of external light and light from an image display device is reflected by a reflective polarizer to generate virtual and real images, the image sharpness sometimes decreases in the conventional reflective polarizers described in Patent Documents 1 and 2. In contrast, it is known that good image sharpness can be obtained by using a reflective circular polarizer having a light-reflecting layer formed by immobilizing a cholesterol-type liquid crystal phase. The inventors believe this is because, by having a light-reflecting layer formed by immobilizing a cholesterol-type liquid crystal phase, a reflective circular polarizer with a high degree of polarization can be realized in a thin film, thus being less susceptible to the effects of foreign matter contamination or fluctuations caused by variations in material density.
[0016] Furthermore, according to the inventors' research, in virtual reality display devices or electronic viewfinders, transmitted light is used in addition to reflected light. In such cases, it becomes important to suppress ghosting caused by the transmission of transmitted light that is intended to be cut off and thus visually perceived. Ghosting suppression has been observed in the existing reflective circular polarizer described in Reference 3, indicating room for further improvement.
[0017] The present invention was made in view of the above-mentioned problems. The technical problem to be solved by the present invention is to provide an optical laminate that produces less ghosting when used in a virtual reality display device or electronic viewfinder, which can be used for a reflective circular polarizer, an optical article having a laminated optical film having the reflective circular polarizer and an optical laminate, and a virtual reality display device including the optical article.
[0018] means for solving technical problems
[0019] The inventors conducted in-depth research on the above-mentioned issues and discovered that the above-mentioned issues can be achieved through the following structure.
[0020] [1] An optical laminate having two or more laminated reflective layers, wherein,
[0021] The aforementioned stacked reflective layers each comprise one of the following reflective layers: reflective layer A, comprising at least one cholesteric liquid crystal layer formed using a first liquid crystal compound substantially composed of rod-shaped liquid crystal compounds, and excluding a cholesteric liquid crystal layer formed using a second liquid crystal compound substantially composed of disk-shaped liquid crystal compounds; and
[0022] Reflective layer B comprises at least one cholesterol-type liquid crystal layer formed using the second liquid crystal compound, which is substantially composed of a disk-shaped liquid crystal compound, and does not comprise a cholesterol-type liquid crystal layer formed using the first liquid crystal compound, which is substantially composed of a rod-shaped liquid crystal compound.
[0023] In the aforementioned stacked reflective layers of two or more layers, when two adjacent stacked reflective layers A are facing each other, the center wavelengths of the reflected light from each of the two adjacent stacked reflective layers A are different.
[0024] In the above-mentioned stacked reflective layers of two or more layers, when the reflective layers B are opposite each other in the stacking direction, the center wavelengths of the reflected light contained in the two adjacent stacked reflective layers B are different.
[0025] [2] According to the optical laminate described in [1], wherein,
[0026] The aforementioned reflective layer A and the aforementioned reflective layer B are alternately arranged in the stacking direction of the aforementioned optical laminate.
[0027] [3] The optical laminate according to [1] or [2], wherein,
[0028] The total number of the aforementioned stacked reflective layers is less than 20.
[0029] [4] An optical laminate according to any one of [1] to [3], wherein,
[0030] The reflectivity of light with wavelengths of 400–700 nm is greater than 40% but less than 50%.
[0031] [5] An optical laminate according to any one of [1] to [4], wherein,
[0032] The aforementioned stacked reflective layer is formed by direct contact between one of the aforementioned reflective layers A and one of the aforementioned reflective layers B, or it is formed by one of the aforementioned reflective layers A, one of the aforementioned reflective layers B, and a sealing layer disposed between the aforementioned reflective layers A and the aforementioned reflective layers B.
[0033] [6] An optical laminate comprising, in sequence, a first layer, a second layer, a third layer and a fourth layer,
[0034] The first through fourth layers mentioned above are all cholesterol-type liquid crystal layers.
[0035] All four layers mentioned above are light reflective.
[0036] The center wavelengths of the reflected light from the first to the fourth layers mentioned above are respectively within any one of the ranges of 430–480 nm, 520–570 nm, 570–620 nm, and 620–670 nm.
[0037] The sign of the film thickness retardation at 550 nm in the first layer is opposite to the sign of the film thickness retardation at 550 nm in the second layer.
[0038] The sign of the retardation in the thickness direction at a wavelength of 550 nm in the third layer is opposite to the sign of the retardation in the thickness direction at a wavelength of 550 nm in the fourth layer.
[0039] [7] The optical laminate according to [6], wherein,
[0040] Of the first layer and the second layer mentioned above, one is a cholesterol-type liquid crystal layer formed using a rod-shaped liquid crystal compound, and the other is a cholesterol-type liquid crystal layer formed using a disk-shaped liquid crystal compound.
[0041] Of the third and fourth layers mentioned above, one is a cholesterol-type liquid crystal layer formed using a rod-shaped liquid crystal compound, and the other is a cholesterol-type liquid crystal layer formed using a disc-shaped liquid crystal compound.
[0042] [8] The optical laminate according to [6] or [7], wherein,
[0043] In the first layer and the fourth layer mentioned above, the center wavelength of the reflected light of one of them is in the range of 430 to 480 nm, and the center wavelength of the reflected light of the other is in the range of 620 to 670 nm.
[0044] [9] An optical laminate according to any one of [6] to [8], wherein,
[0045] The center wavelength of the reflected light from the first layer mentioned above is in the range of 430–480 nm.
[0046] The center wavelength of the reflected light from the second layer mentioned above is in the range of 520–570 nm.
[0047] The center wavelength of the reflected light from the third layer mentioned above is in the range of 570–620 nm.
[0048] The center wavelength of the reflected light from the fourth layer mentioned above is in the range of 620 to 670 nm.
[0049]
[10] An optical laminate comprising a first layer, a second layer and a third layer in sequence,
[0050] The first to the third layers mentioned above are all cholesterol-type liquid crystal layers.
[0051] The second layer mentioned above is a pitch gradient layer formed by the variation of the helical pitch in the film thickness direction.
[0052] All three layers mentioned above are light reflective.
[0053] The center wavelengths of the reflected light from the first to the third layers mentioned above are respectively within any one of the ranges of 430–480 nm, 520–620 nm, and 620–670 nm.
[0054] The sign of the film thickness retardation at 550 nm in the first layer is opposite to the sign of the film thickness retardation at 550 nm in the second layer.
[0055] The sign of the retardation in the thickness direction at a wavelength of 550 nm in the second layer is opposite to the sign of the retardation in the thickness direction at a wavelength of 550 nm in the third layer.
[0056]
[11] The optical laminate according to
[10] , wherein,
[0057] The first layer described above is a cholesterol-type liquid crystal layer formed using rod-shaped liquid crystal compounds; the second layer described above is a cholesterol-type liquid crystal layer formed using disk-shaped liquid crystal compounds; and the third layer described above is a cholesterol-type liquid crystal layer formed using rod-shaped liquid crystal compounds, or...
[0058] The first layer is a cholesterol-type liquid crystal layer formed using a disc-shaped liquid crystal compound, the second layer is a cholesterol-type liquid crystal layer formed using a rod-shaped liquid crystal compound, and the third layer is a cholesterol-type liquid crystal layer formed using a disc-shaped liquid crystal compound.
[0059]
[12] The optical laminate according to
[10] or
[11] , wherein,
[0060] The center wavelength of the reflected light from the first layer mentioned above is in the range of 430–480 nm.
[0061] The center wavelength of the reflected light from the second layer mentioned above is in the range of 520–620 nm.
[0062] The center wavelength of the reflected light from the third layer is in the range of 620–670 nm.
[0063]
[13] A stacked optical film, comprising at least sequentially a reflective circular polarizer, a phase difference layer for converting circularly polarized light into linearly polarized light, and a linear polarizer, wherein,
[0064] The aforementioned reflective circular polarizer is any one of the optical laminates described in [1] to
[12] .
[0065]
[14] According to the stacked optical film described in
[13] , wherein,
[0066] The linear polarizer includes at least a light-absorbing anisotropic layer comprising a liquid crystal compound and a dichroic material.
[0067]
[15] The laminated optical film according to
[13] or
[14] further comprises a positive C-plate.
[0068]
[16] The laminated optical film according to any one of
[13] to
[15] further comprises an anti-reflective layer on its surface.
[0069]
[17] According to the stacked optical film described in
[16] , wherein,
[0070] The aforementioned anti-reflective layer is either a moth-eye film or an AR film.
[0071]
[18] The laminated optical film according to any one of
[13] to
[17] , comprising:
[0072] Resin substrates with a tanδ peak temperature below 170℃.
[0073]
[19] An optical article comprising any one of the optical laminates described in [1] to
[12] .
[0074]
[20] A virtual reality display device comprising the optical article described in
[19] .
[0075] Invention Effects
[0076] The present invention provides an optical laminate that produces less ghosting when used in virtual reality display devices or electronic viewfinders, and can be used in reflective circular polarizers.
[0077] Furthermore, according to the present invention, it is possible to provide an optical article having a laminated optical film having the above-mentioned reflective circular polarizer and an optical laminate having the above-mentioned optical laminate, as well as a virtual reality display device including the optical article. Attached Figure Description
[0078] Figure 1 This is a schematic diagram illustrating an example of an optical laminate according to the first embodiment of the present invention.
[0079] Figure 2 This is a schematic diagram illustrating an example of an optical laminate according to the first embodiment of the present invention.
[0080] Figure 3This is a schematic diagram illustrating an example of a second embodiment of the optical laminate of the present invention.
[0081] Figure 4 This is a schematic diagram illustrating an example of an optical laminate according to a third embodiment of the present invention.
[0082] Figure 5 This is an example of a virtual reality display device using the stacked optical film of the present invention.
[0083] Figure 6 This is an example of a virtual reality display device using the stacked optical film of the present invention.
[0084] Figure 7 This is a schematic diagram illustrating an example of the stacked optical film of the present invention. Detailed Implementation
[0085] The present invention will now be described in detail. The description of the constituent elements described below is sometimes based on representative embodiments or specific examples, but the present invention is not limited to such embodiments.
[0086] In addition, in this specification, the numerical range indicated by “~” refers to the range including the values recorded before and after “~” as the lower limit and upper limit values.
[0087] In this specification, "orthogonal" does not mean 90° in the strict sense, but rather 90° ± 10°, preferably 90° ± 5°. Similarly, "parallel" does not mean 0° in the strict sense, but rather 0° ± 10°, preferably 0° ± 5°. Furthermore, "45°" does not mean 45° in the strict sense, but rather 45° ± 10°, preferably 45° ± 5°.
[0088] In this specification, "absorption axis" refers to the polarization direction in which the absorbance is greatest when incident on linearly polarized light. "Reflection axis" refers to the polarization direction in which the reflectivity is greatest when incident on linearly polarized light. "Transmission axis" refers to the direction in which the light is orthogonal to either the absorption or reflection axis. Furthermore, "slow axis" refers to the direction in which the refractive index is greatest when incident on linearly polarized light.
[0089] In this specification, unless otherwise specified, phase difference refers to in-plane delay, denoted as Re(λ). Here, Re(λ) represents the in-plane delay at wavelength λ, which is set to 550 nm unless otherwise specified.
[0090] Furthermore, the thickness direction delay at wavelength λ is described in this specification as Rth(λ).
[0091] Re(λ) and Rth(λ) can be obtained using an AxoScan OPMF-1 (manufactured by Opto Science, Inc.) at wavelength λ. The values are calculated by inputting the average refractive index ((nx+ny+nz) / 3) and film thickness (d(μm)) into AxoScan.
[0092] Slow axis direction (°)
[0093] Re(λ)=R0(λ)
[0094] Rth(λ)=((nx+ny) / 2-nz)×d.
[0095] Examples of optical laminates for the present invention include a first embodiment, a second embodiment, and a third embodiment.
[0096] Hereinafter, the first, second and third embodiments of the optical laminate of the present invention will be described.
[0097] [First Implementation Method]
[0098] The optical laminate of the first embodiment of the present invention has two or more laminated reflective layers.
[0099] The above-mentioned stacked reflective layers each contain one of the following reflective layers:
[0100] Reflective layer A comprises at least one cholesterol-type liquid crystal layer (hereinafter also referred to as "liquid crystal layer 1") formed using a first liquid crystal compound substantially composed of rod-shaped liquid crystal compounds, and does not comprise a cholesterol-type liquid crystal layer (hereinafter also referred to as "liquid crystal layer 2") formed using a second liquid crystal compound substantially composed of disk-shaped liquid crystal compounds; and
[0101] Reflective layer B comprises at least one liquid crystal layer 2, but does not comprise liquid crystal layer 1.
[0102] In the aforementioned stacked reflective layers of two or more layers, when two adjacent stacked reflective layers A are facing each other, the center wavelengths of the reflected light from each of the two adjacent stacked reflective layers A are different.
[0103] In the above-mentioned stacked reflective layers of two or more layers, when the reflective layers B are opposite each other in the stacking direction, the center wavelengths of the reflected light contained in the two adjacent stacked reflective layers B are different.
[0104] The optical laminate of the first embodiment of the present invention will be described with reference to the accompanying drawings. Figure 1This is a schematic cross-sectional view showing an example of the structure of the optical laminate 10 of the first embodiment.
[0105] exist Figure 1 In the illustrated configuration, the optical laminate 10 comprises a first stacked reflective layer 25 and a second stacked reflective layer 26. The first stacked reflective layer 25 comprises reflective layer A21a and reflective layer B22b, and the second stacked reflective layer 26 comprises reflective layer A23a and reflective layer B24b. Figure 1 In the optical laminate 10 shown, reflective layer A21a, reflective layer B22b, reflective layer A23a and reflective layer B24b are stacked sequentially.
[0106] The optical laminate of the first embodiment of the present invention can be used in a reflective circular polarizer. If the optical laminate has the structure described above, then the reflective layer A has a positive Rth and the reflective layer B has a negative Rth. Therefore, it is assumed that their Rth values cancel each other out, and ghosting can be suppressed even for incident light from an oblique direction.
[0107] The first embodiment of the present invention will now be described in detail.
[0108] [Layered reflective layer]
[0109] The optical laminate of the first embodiment of the present invention has two or more stacked reflective layers, each of which includes a reflective layer A and a reflective layer B, which will be described in detail later. That is, the optical laminate of the first embodiment of the present invention includes two or more reflective layers A and B.
[0110] In a stacked reflective layer, reflective layer A and reflective layer B can be in direct contact, or they can be stacked via other layers. There are no particular limitations on these other layers, but examples include bonding layers (e.g., adhesive layers, bonding agents, etc.), refractive index adjustment layers, resin films, positive C-plates, and alignment layers.
[0111] Furthermore, the stacked reflective layer can be formed by one reflective layer A and one reflective layer B in direct contact, or it can be formed by one reflective layer A, one reflective layer B, and a sealing layer disposed between reflective layer A and reflective layer B. Preferably, the stacked reflective layer is formed by one reflective layer A and one reflective layer B in direct contact.
[0112] In optical laminates, the reflective layers can be stacked in a manner where reflective layer A and reflective layer B are arranged alternately, or in a manner where reflective layer A is placed opposite each other, or in a manner where reflective layer B is placed opposite each other.
[0113] For example, in the case where the optical laminate of the first embodiment has two stacked reflective layers, it can be stacked in the order of reflective layer A, reflective layer B, reflective layer A and reflective layer B, reflective layer A, reflective layer B and reflective layer A, or reflective layer B, reflective layer A, reflective layer A and reflective layer B.
[0114] However, in two adjacent stacked reflective layers in the stacking direction, when the reflective layers A are opposite each other (for example, when stacked in the order of reflective layer B, reflective layer A, reflective layer A and reflective layer B), the center wavelengths of the reflected light contained in the two adjacent stacked reflective layers A are different. In two or more stacked reflective layers, in two adjacent stacked reflective layers in the stacking direction, when the reflective layers B are opposite each other (for example, when stacked in the order of reflective layer A, reflective layer B, reflective layer B and reflective layer A), the center wavelengths of the reflected light contained in the two adjacent stacked reflective layers B are different.
[0115] The following description uses the accompanying drawings to illustrate an optical laminate in which two adjacent reflective layers A are positioned opposite each other in the stacking direction. Figure 2 The optical laminate 11 shown is composed of a first stacked reflective layer 25 and a second stacked reflective layer 26. The first stacked reflective layer 25 is composed of reflective layer B21b and reflective layer A22a, and the second stacked reflective layer 26 is composed of reflective layer A23a and reflective layer B24b. Figure 2 In the optical laminate 11 shown, reflective layer B21b, reflective layer A22a, reflective layer A23a, and reflective layer B24b are stacked sequentially. However, the center wavelength of the reflected light from reflective layer A22a is different from the center wavelength of the reflected light from reflective layer A23a. Furthermore, in Figure 2 In the optical laminate 11 shown, reflective layer A22a is included in the first reflective layer 25, and reflective layer A23a is included in the second reflective layer 26.
[0116] That is, as will be described in detail later, the reflective layer A may contain two or more liquid crystal layers 1 with different center wavelengths of reflected light. However, in the case of two or more liquid crystal layers 1 being arranged in succession in the optical laminate, the reflective layer A and the laminated reflective layer are used to maximize the number of laminated reflective layers.
[0117] Similarly, as will be described in detail later, the reflective layer B may contain two or more liquid crystal layers 2 with different center wavelengths of reflected light. However, in optical laminates, when two or more liquid crystal layers 2 are arranged consecutively, a reflective layer B and a stacked reflective layer are used to maximize the number of stacked reflective layers.
[0118] The preferred method for stacking the aforementioned reflective layers is to stack reflective layer A and reflective layer B alternately. That is, it is preferable that reflective layer A and reflective layer B are arranged alternately in the thickness direction of the optical laminate.
[0119] The optical laminate of the first embodiment includes two or more stacked reflective layers, but may also include three or more stacked reflective layers, or four or more. That is, the optical laminate includes two or more of the above-mentioned reflective layer A and reflective layer B, but may also include three or more of the above-mentioned reflective layer A and reflective layer B, or four or more of each.
[0120] The total number of reflective layers in the optical laminate is preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less. That is, the total number of reflective layers A and B in the optical laminate is preferably 60 or less, more preferably 40 or less, and even more preferably 20 or less.
[0121] The thickness of the stacked reflective layer is preferably 0.2 μm or more, more preferably 0.4 μm or more, and even more preferably 0.6 μm or more. Furthermore, the thickness of the stacked reflective layer is preferably 20.0 μm or less, more preferably 14.0 μm or less, and even more preferably 10.0 μm or less.
[0122] The thickness of the stacked reflective layers was measured using the same method as that used for reflective layers A and B, which are described later.
[0123] The following is a description of reflective layer A and reflective layer B.
[0124] [Reflective layer A]
[0125] The optical laminate of the first embodiment of the present invention includes at least one liquid crystal layer 1 and includes a reflective layer A that does not include a liquid crystal layer 2.
[0126] Liquid crystal layer 1 is a cholesterol-type liquid crystal layer formed using a first liquid crystal compound that is substantially composed of rod-shaped liquid crystal compounds. Furthermore, "a cholesterol-type liquid crystal layer formed using a first liquid crystal compound that is substantially composed of rod-shaped liquid crystal compounds" means a layer formed by fixing the orientation state of the cholesterol-type liquid crystal phase by setting the first liquid crystal compound as a cholesterol-type liquid crystal phase. The phrase "substantially composed of rod-shaped liquid crystal compounds" means that the rod-shaped liquid crystal compound constitutes 95% or more of the liquid crystal compound (first liquid crystal compound) contained in liquid crystal layer 1. That is, "substantially composed of rod-shaped liquid crystal compounds" means that the content of the rod-shaped liquid crystal compound relative to the total mass of the first liquid crystal compound is 95% or more. Preferably, the first liquid crystal compound is composed only of rod-shaped liquid crystal compounds.
[0127] Furthermore, the liquid crystal layer 2 is a cholesterol-type liquid crystal layer formed using a second liquid crystal compound that is substantially composed of a disk-shaped liquid crystal compound. Additionally, "a cholesterol-type liquid crystal layer formed using a second liquid crystal compound that is substantially composed of a disk-shaped liquid crystal compound" means that the second liquid crystal compound is a cholesterol-type liquid crystal phase, and the orientation state of the cholesterol-type liquid crystal phase is fixed to form a layer. The phrase "substantially composed of a disk-shaped liquid crystal compound" means that the disk-shaped liquid crystal compound constitutes 95% or more of the liquid crystal compound (second liquid crystal compound) contained in the liquid crystal layer 2. That is, "substantially composed of a second liquid crystal compound" means that the content of the disk-shaped liquid crystal compound relative to the total mass of the second liquid crystal compound is 95% or more. Preferably, the second liquid crystal compound is composed only of disk-shaped liquid crystal compounds.
[0128] The reflective layer A may contain one or more liquid crystal layers 1, or it may contain two or more. If the reflective layer A contains two or more liquid crystal layers 1, other layers besides liquid crystal layer 2 may or may not be included between the two or more liquid crystal layers 1. There are no particular restrictions on these other layers, but examples include bonding layers (e.g., adhesive layers, bonding layers, etc.), refractive index adjustment layers, resin films, positive C-plates, and alignment layers.
[0129] The number of liquid crystal layers 1 included in the reflective layer A is preferably 5 or less, more preferably 3 or less, and even more preferably 2 or less. The number of liquid crystal layers 1 included in the reflective layer A is preferably 1.
[0130] Furthermore, for example, if two liquid crystal layers 1 have different center wavelengths of reflected light, they are considered as two liquid crystal layers 1. Moreover, as long as two or more liquid crystal layers 1 have the same center wavelength of reflected light, they are considered as one liquid crystal layer 1, whether they are formed by sequential coating or separated by the other layers mentioned above.
[0131] When the reflective layer A contains two or more liquid crystal layers 1, the center wavelength of the reflected light from the reflective layer A is set as the center wavelength of the reflected light from the entire reflective layer A. The method for measuring the center wavelength of the reflected light is described below.
[0132] The thickness of the reflective layer A is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. At points where ghosting can be further suppressed, the thickness of the reflective layer A is preferably 10.0 μm or less, more preferably 7.0 μm or less, and even more preferably 5.0 μm or less.
[0133] The thickness of reflective layer A was measured by fabricating a cross-section of the optical laminate and observing it using a scanning electron microscope. The thickness of reflective layer A was defined as the average thickness of reflective layer A at any five points along the cross-section of the optical laminate. Furthermore, when observing the cross-section of the optical laminate using a scanning electron microscope, the regions of reflective layer A and reflective layer B (described later) could be distinguished by differences in the contrast of the photographed images. Moreover, the regions of reflective layer A and reflective layer B could also be distinguished by using compositional analysis along the film thickness using Time-of-Flight-Secondary Ion Mass Spectrometry (TOF-SIMS).
[0134] The Rth of the reflective layer A is at a wavelength of 550 nm, preferably 8–800 nm, more preferably 16–560 nm, and even more preferably 24–400 nm.
[0135] The Rth of reflective layer A can be measured by taking only reflective layer A out of the optical laminate, or by measuring the Rth of a layer made under the same conditions as when reflective layer A was made.
[0136] There are no particular limitations on the rod-shaped liquid crystal compound contained in the liquid crystal layer 1, and any known rod-shaped liquid crystal compound can be used. Furthermore, liquid crystal layer 1 only needs to be a layer in which the orientation of the rod-shaped liquid crystal compound, which is a cholesterol-type liquid crystal phase, is maintained. Typically, this can be achieved by adding chiral reagents or other methods to orient a polymerizable rod-shaped liquid crystal compound with polymerizable groups into a cholesterol-type liquid crystal phase, followed by polymerization and curing via ultraviolet irradiation, heating, etc., to form a non-flowing layer. As described above, liquid crystal layer 1 only needs to be a layer whose orientation morphology does not change due to external fields or forces. Additionally, in liquid crystal layer 1, it is sufficient that the optical properties of the cholesterol-type liquid crystal phase are maintained within the layer; the rod-shaped liquid crystal compound in liquid crystal layer 1 does not need to exhibit liquid crystal properties. For example, the polymerizable rod-shaped liquid crystal compound can be molecularized through a curing reaction, thereby losing its liquid crystal properties.
[0137] The center wavelength λ of the reflected light from liquid crystal layer 1 depends on the pitch P (=the period of the helix) of the helical structure in the cholesterol-type liquid crystal phase, and is expressed by the relationship λ=n×P using the average refractive index n of liquid crystal layer 1. Furthermore, the center wavelength of the reflected light from liquid crystal layer 1 can be determined as follows: When measuring the transmission spectrum of reflective layer A from the normal direction of liquid crystal layer 1 using a spectrophotometer UV3150 (SHIMADZU CORPORATION), a spectrum with a peak of decreased transmittance is obtained in the region near the center wavelength of the reflected light. Among the two wavelengths of transmittance that represent half the maximum peak value, the shorter wavelength side is defined as λ. l (nm), where the wavelength value on the longer wavelength side is set to λ. h The center wavelength λ of the reflected light (nm) is obtained by the following formula.
[0138] λ=(λ l +λ h ) / 2
[0139] The pitch of the cholesterol-type liquid crystal phase varies depending on the type and concentration of the chiral reagent used with the polymerizable rod-shaped liquid crystal compound. By adjusting any one or more of the above, a cholesterol-type liquid crystal phase with the desired pitch can be obtained. Furthermore, the methods for measuring the rotation direction and pitch of the helix can be found in "Introduction to Liquid Crystal Chemistry Experiments," edited by the Japan Liquid Crystal Society, published by Sigma in 2007, page 46, and in "Liquid Crystal Handbook," edited by Maruzen of the Liquid Crystal Handbook Editorial Committee, page 196.
[0140] [Reflective layer B]
[0141] The optical laminate of the first embodiment of the present invention includes at least one liquid crystal layer 2 and includes a reflective layer B that does not include the liquid crystal layer 1.
[0142] The definitions of liquid crystal layer 2 and liquid crystal layer 1 are as described above.
[0143] The reflective layer B may contain one or more liquid crystal layers 2, or it may contain two or more. If the reflective layer B contains two or more liquid crystal layers 2, other layers besides liquid crystal layer 1 may or may not be included between the two or more liquid crystal layers 2. There are no particular restrictions on these other layers, but examples include bonding layers (e.g., adhesive layers, bonding agents, etc.), refractive index adjustment layers, resin films, positive C-plates, and alignment layers.
[0144] The number of liquid crystal layers 2 included in the reflective layer B is preferably 5 or less, more preferably 3 or less, and even more preferably 2 or less. The number of liquid crystal layers 2 included in the reflective layer B is preferably 1.
[0145] Furthermore, for example, if two liquid crystal layers 2 have different center wavelengths of reflected light, they are considered as two liquid crystal layers 2. Moreover, as long as two or more liquid crystal layers 2 have the same center wavelength of reflected light, they are considered as one liquid crystal layer 2, whether they are formed by sequential coating or separated by the other layers mentioned above.
[0146] When the reflective layer B contains two or more liquid crystal layers 2, the center wavelength of the reflected light from the reflective layer B is set as the center wavelength of the reflected light from the entire reflective layer B. The center wavelength of the reflected light from each liquid crystal layer 2 is measured according to the method for measuring the center wavelength of the reflected light from the liquid crystal layer 1 described above.
[0147] The thickness of the reflective layer B is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. At points where ghosting can be further suppressed, the thickness of the reflective layer B is preferably 10.0 μm or less, more preferably 7.0 μm or less, and even more preferably 5.0 μm or less.
[0148] The thickness of reflective layer B was measured by fabricating a cross-section of an optical laminate and observing it using a transmission electron microscope.
[0149] The Rth of the reflective layer B is at a wavelength of 550 nm, preferably -8 to -800 nm, more preferably -16 to -560 nm, and even more preferably -24 to -400 nm.
[0150] The Rth of reflective layer B can be measured by taking only reflective layer B out of the optical laminate, or by measuring the Rth of a layer made under the same conditions as when reflective layer B was made.
[0151] There are no particular limitations on the disc-shaped liquid crystal compound contained in the liquid crystal layer 2, and any known disc-shaped liquid crystal compound can be used. Furthermore, liquid crystal layer 2 only needs to be a layer in which the orientation of the disc-shaped liquid crystal compound, which is a cholesterol-type liquid crystal phase, is maintained. Typically, a polymerizable disc-shaped liquid crystal compound with polymerizable groups can be oriented to a cholesterol-type liquid crystal phase by adding chiral reagents or other methods, and then polymerized and cured by ultraviolet irradiation, heating, etc., to form a non-flowing layer. As described above, liquid crystal layer 2 only needs to be a layer whose orientation morphology will not change due to external fields or external forces. In addition, in liquid crystal layer 2, it is sufficient that the optical properties of the cholesterol-type liquid crystal phase can be maintained within the layer; the disc-shaped liquid crystal compound in liquid crystal layer 2 does not need to exhibit liquid crystal properties. For example, the polymerizable disc-shaped liquid crystal compound can be molecularized through a curing reaction, thereby losing its liquid crystal properties.
[0152] The center wavelength λ of the reflected light from liquid crystal layer 2 depends on the pitch of the helical structure in the cholesterol-type liquid crystal phase, and can be defined in the same way as in the case of liquid crystal layer 1, and measured using the same method.
[0153] The pitch of the cholesterol-type liquid crystal phase varies depending on the type and concentration of the chiral reagent used with the polymerizable disk-shaped liquid crystal compound. By adjusting any one or more of the above, a cholesterol-type liquid crystal phase with the desired pitch can be obtained. Furthermore, the methods for determining the helical rotation direction and pitch can be found in the aforementioned literature.
[0154] [Reflectivity]
[0155] In the first embodiment of the present invention, the reflectivity of the optical laminate with a wavelength of 400-700 nm is preferably 40% or more and less than 50%. When the reflectivity is 40% or more, ghosting is easily suppressed. Furthermore, the light with a wavelength of 400-700 nm mentioned above refers to unpolarized light.
[0156] The reflectivity of optical laminates for wavelengths of 400–700 nm was measured under the following conditions.
[0157] An automated absolute reflectance measurement system consisting of a JASCO Corporation V-750 UV-Vis-NIR spectrophotometer was used. For the optical laminate, S-wave and P-wave polarized light with wavelengths of 350–900 nm was incident at an angle of 5°. The absolute reflectance for each S-wave and P-wave was measured, and the average value was calculated for each wavelength to obtain the reflectance spectrum. From the obtained reflectance spectrum, the average reflectance for light with wavelengths of 400–700 nm was calculated and set as the reflectance of the optical laminate for light with wavelengths of 400–700 nm.
[0158] [Types and configurations of reflective layer A and reflective layer B]
[0159] The optical laminate of the first embodiment of the present invention includes the aforementioned reflective layer A and reflective layer B, but preferably includes at least a blue light reflective layer with a reflectivity of 40% or more at a wavelength of 460 nm, a green light reflective layer with a reflectivity of 40% or more at a wavelength of 550 nm, a yellow light reflective layer with a reflectivity of 40% or more at a wavelength of 600 nm, and a red light reflective layer with a reflectivity of 40% or more at a wavelength of 650 nm. The aforementioned blue, green, yellow, and red light reflective layers can each correspond to any one of reflective layer A and reflective layer B. For example, when reflective layer A corresponds to the blue light reflective layer, the center wavelength of the reflected light from reflective layer A can be adjusted using the above method to set the center wavelength of the reflected light to approximately 460 nm. Similarly, when reflective layer B corresponds to the blue light reflective layer, the center wavelength of the reflected light from reflective layer B can be adjusted using the above method to set the center wavelength of the reflected light to approximately 460 nm. Furthermore, the aforementioned reflectivity refers to the reflectivity of the reflective layers when unpolarized light is incident at their respective wavelengths.
[0160] When an optical laminate includes the aforementioned blue light reflective layer, green light reflective layer, yellow light reflective layer, and red light reflective layer, it may have two or more blue light reflective layers, two or more green light reflective layers, two or more yellow light reflective layers, or two or more red light reflective layers.
[0161] The center wavelength of the reflected light from the aforementioned blue light reflective layer is preferably in the range of 430–480 nm.
[0162] The center wavelength of the reflected light from the aforementioned green light reflective layer is preferably in the range of 520–570 nm.
[0163] The center wavelength of the reflected light from the aforementioned yellow light-reflecting layer is preferably in the range of 570–620 nm.
[0164] The center wavelength of the reflected light from the aforementioned red light reflective layer is preferably in the range of 620–670 nm.
[0165] The method for determining the center wavelength of the reflected light is as described above.
[0166] Furthermore, in the optical laminate of the first embodiment of the present invention, the center wavelengths of the reflected light of the reflective layer A and the reflective layer B included in the optical laminate can be adjusted to cover the entire visible light region (wavelength 400-700nm) so that the reflectivity is 40% or more.
[0167] Furthermore, the optical laminate preferably comprises, in sequence, the aforementioned blue light reflecting layer, green light reflecting layer, yellow light reflecting layer, and red light reflecting layer. Moreover, when the optical laminate with the aforementioned stacking order is applied to the reflective circular polarizer described later, in the long-wavelength side reflective layer (e.g., the red light reflecting layer), the thickness of the reflective layer required to obtain sufficient reflectivity increases. At the point where the influence of the reflective layer's own Rth on the light transmitted through the reflective layer becomes greater, the reflective layer disposed on the light source side is preferably a short-wavelength side reflective layer (e.g., the blue light reflecting layer).
[0168] In the optical laminate of the first embodiment of the present invention, the reflective layer A has a positive Rth and the reflective layer B has a negative Rth. Therefore, their Rth values cancel each other out. This has been described above, but the details are explained below.
[0169] In an optical laminate with n reflective layers, the reflective layers are named sequentially from the light source side as L1, L2, L3, ..., L... n When n is an integer greater than or equal to 4, the distance from reflector L1 to reflector L... i Let SRth be the sum of Rth for each level (where i is an integer less than or equal to n). i Specifically, SRth i As shown below.
[0170] SRth1 = Rth1
[0171] SRth2 = Rth1 + Rth2
[0172] …
[0173] SRth i =Rth1+Rth2+…+Rth i
[0174] …
[0175] SRth n =Rth1+Rth2+…+Rth i +…+Rth n
[0176] All of these SRth i (SRth1~SRth n The absolute values of Rth for each layer are preferably 0.3 μm or less, more preferably 0.2 μm or less, and even more preferably 0.1 μm or less. i The formula for calculating Rth, as described above, can be used to obtain the result.
[0177] It is believed that by SRth iWithin the aforementioned preferred range, the phase difference generated when transmitting through each reflective layer can be reduced, and the generation of ghosting can be further suppressed for incident light from the tilted direction.
[0178] Furthermore, in the case where reflective layer A and reflective layer B are directly in contact within a stacked reflective layer, in order to reduce the refractive index difference, it is preferable to arrange the liquid crystal compound (rod-shaped liquid crystal compound or disk-shaped liquid crystal compound) in such a way that the orientation direction (slow axis direction) continuously changes at the interface. In the configuration described above, for example, when reflective layer A is formed on reflective layer B, a coating liquid containing a rod-shaped liquid crystal compound can also be directly coated onto reflective layer B, and the orientation can be performed continuously at the interface in the slow axis direction based on the orientation restraint force of the disk-shaped liquid crystal compound contained in reflective layer B.
[0179] The thickness of the optical laminate in the first embodiment of the present invention is preferably 30 μm or less, and more preferably 15 μm or less.
[0180] There are no particular restrictions on the lower limit; for example, 1 μm or more is acceptable, and 5 μm or more is preferred.
[0181] The manufacturing method of the optical laminate according to the first embodiment of the present invention, and the laminated optical film using the optical laminate, will be described later.
[0182] [Second Implementation]
[0183] The optical laminate of the second embodiment of the present invention comprises a first layer, a second layer, a third layer, and a fourth layer in sequence.
[0184] The first through fourth layers mentioned above are all cholesterol-type liquid crystal layers.
[0185] All four layers mentioned above are light reflective.
[0186] The center wavelengths of the reflected light from the first to the fourth layers mentioned above are respectively within any one of the ranges of 430–480 nm, 520–570 nm, 570–620 nm, and 620–670 nm.
[0187] The sign of Rth at a wavelength of 550 nm in the first layer is opposite to the sign of Rth at a wavelength of 550 nm in the second layer.
[0188] The sign of Rth at a wavelength of 550nm in the third layer is opposite to the sign of Rth at a wavelength of 550nm in the fourth layer.
[0189] The optical laminate of the second embodiment of the present invention will be described with reference to the accompanying drawings. Figure 3This is a schematic cross-sectional view showing an example of the structure of the optical laminate 12 of the second embodiment.
[0190] exist Figure 3 In the manner shown, the optical laminate 12 consists of a first layer 31, a second layer 32, a third layer 33, and a fourth layer 34, which respectively satisfy the aforementioned necessary conditions. Furthermore, the sign of Rth for the first layer 31 is opposite to that for the second layer 32, and the sign of Rth for the third layer 33 is opposite to that for the fourth layer 34.
[0191] The optical laminate of the second embodiment of the present invention can be used in a reflective circular polarizer. It is believed that if the optical laminate has the above-described structure, the Rth values of the first layer and the second layer cancel each other out, and the Rth values of the third layer and the fourth layer also cancel each other out. Therefore, the generation of ghosting can be suppressed even for incident light from the tilted direction.
[0192] The second embodiment of the present invention will now be described in detail.
[0193] [First to Fourth Floors]
[0194] The optical laminate of the second embodiment of the present invention comprises a first layer, a second layer, a third layer and a fourth layer in sequence.
[0195] The first to fourth layers mentioned above are cholesterol-type liquid crystal layers with light reflectivity.
[0196] The aforementioned cholesterol-type liquid crystal layer refers to a layer formed by immobilizing a cholesterol-type liquid crystal phase with a liquid crystal compound. Known cholesterol-type liquid crystal layers can be used as such layers; for example, the liquid crystal layer described in Japanese Patent Application Publication No. 2020-060627, etc.
[0197] The aforementioned cholesterol-type liquid crystal layer is preferably a cholesterol-type liquid crystal layer formed using rod-shaped liquid crystal compounds, or a cholesterol-type liquid crystal layer formed using disk-shaped liquid crystal compounds. In cholesterol-type liquid crystal layers formed using rod-shaped liquid crystal compounds, Rth tends to be a positive value, while in cholesterol-type liquid crystal layers formed using disk-shaped liquid crystal compounds, Rth tends to be a negative value.
[0198] Furthermore, the center wavelengths of the reflected light from the first to the fourth layers are respectively within any one of the ranges of 430–480 nm, 520–570 nm, 570–620 nm, and 620–670 nm. Preferably, the center wavelengths of the reflected light from the first to the fourth layers are also different.
[0199] When the center wavelength of the reflected light is 430–480 nm, this layer can correspond to the blue light reflecting layer described in the first embodiment. In this case, the reflectivity at the center wavelength of the reflected light is preferably 40% or more and less than 50%.
[0200] When the center wavelength of the reflected light is 520–570 nm, this layer can correspond to the green light reflective layer described in the first embodiment. In this case, the reflectivity at the center wavelength of the reflected light is preferably 40% or more and less than 50%.
[0201] When the center wavelength of the reflected light is 570–620 nm, this layer can correspond to the yellow light-reflecting layer described in the first embodiment. In this case, the reflectivity at the center wavelength of the reflected light is preferably 40% or more and less than 50%.
[0202] When the center wavelength of the reflected light is 620–670 nm, this layer can correspond to the red light reflecting layer described in the first embodiment. In this case, the reflectivity at the center wavelength of the reflected light is preferably 40% or more and less than 50%.
[0203] The method for measuring reflectance is as described above.
[0204] The center wavelengths of the reflected light from the first to the fourth layers can be within any of the aforementioned wavelength ranges. However, in the first and fourth layers, it is preferred that the center wavelength of one reflected light is in the range of 430–480 nm, and the center wavelength of the other reflected light is in the range of 620–670 nm.
[0205] Furthermore, it is also preferred that the center wavelength of the reflected light of the first layer is in the range of 430 to 480 nm, the center wavelength of the reflected light of the second layer is in the range of 520 to 570 nm, the center wavelength of the reflected light of the third layer is in the range of 570 to 620 nm, and the center wavelength of the reflected light of the fourth layer is in the range of 620 to 670 nm.
[0206] That is, it is also preferred that the first layer corresponds to the blue light reflective layer, the second layer corresponds to the green light reflective layer, the third layer corresponds to the yellow light reflective layer, and the fourth layer corresponds to the red light reflective layer.
[0207] Furthermore, when the optical laminate with the stacking order described above is applied to the reflective circular polarizer described later, in the long-wavelength side reflective layer (e.g., red light reflective layer), the thickness of the reflective layer required to obtain sufficient reflectivity becomes thicker. At the point where the influence of the reflective layer's own Rth on the light transmitted through the reflective layer becomes greater, the reflective layer disposed on the light source side is preferably a short-wavelength side reflective layer (e.g., blue light reflective layer).
[0208] In the optical laminate of the second embodiment of the present invention, the sign of Rth at a wavelength of 550 nm in the first layer is opposite to the sign of Rth at a wavelength of 550 nm in the second layer, and the sign of Rth at a wavelength of 550 nm in the third layer is opposite to the sign of Rth at a wavelength of 550 nm in the fourth layer.
[0209] As mentioned above, there are no particular limitations on the method of reversing the sign of Rth in the first and second layers. For example, one of the first and second layers can be a cholesteric liquid crystal layer formed using a rod-shaped liquid crystal compound, and the other can be a cholesteric liquid crystal layer formed using a disc-shaped liquid crystal compound.
[0210] Similarly, as mentioned above, there are no particular restrictions on the method of reversing the sign of Rth in the third and fourth layers. For example, one of the third and fourth layers can be a cholesteric liquid crystal layer formed using a rod-shaped liquid crystal compound, and the other can be a cholesteric liquid crystal layer formed using a disc-shaped liquid crystal compound.
[0211] Furthermore, it is preferable that the signs of Rth are reversed in the second and third layers. For example, the following arrangements can be made: the first and third layers are cholesterol-type liquid crystal layers formed using rod-shaped liquid crystal compounds, and the second and fourth layers are cholesterol-type liquid crystal layers formed using disk-shaped liquid crystal compounds; and the first and third layers are cholesterol-type liquid crystal layers formed using disk-shaped liquid crystal compounds, and the second and fourth layers are cholesterol-type liquid crystal layers formed using rod-shaped liquid crystal compounds.
[0212] The thicknesses of the first to fourth layers are preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. At points where ghosting can be further suppressed, the thicknesses of the first to fourth layers are preferably 10.0 μm or less, more preferably 7.0 μm or less, and even more preferably 5.0 μm or less.
[0213] The thickness of the first to fourth layers can be measured by fabricating a cross-section of the optical laminate and observing it with a transmission electron microscope.
[0214] Furthermore, in the optical laminate of the second embodiment, the SRth described in the optical laminate of the first embodiment... i The absolute values of these values are preferably within the ranges described above. Furthermore, in the definitions described above for the optical laminate of the first embodiment, n can be replaced with 4.
[0215] Specifically, SRth iThe absolute values are preferably 0.3 μm or less, more preferably 0.2 μm or less, and even more preferably 0.1 μm or less.
[0216] It is believed that by SRth i Within the aforementioned preferred range, the phase difference generated when transmitting through each reflective layer can be reduced, and the generation of ghosting can be further suppressed for incident light from the tilted direction.
[0217] In the optical laminate of the second embodiment of the present invention, the first to fourth layers can be laminated in direct contact with each other, or they can be laminated via other layers. There are no particular limitations on the other layers, but examples include bonding layers (e.g., adhesive layers, bonding layers, etc.), refractive index adjustment layers, resin films, positive C-plates, and alignment layers. Preferably, the first to fourth layers are laminated in direct contact with each other.
[0218] Furthermore, in the optical laminate of the second embodiment of the present invention, when the first to fourth layers are stacked in direct contact with each other, in order to reduce the refractive index difference, it is preferable to arrange the liquid crystal compound (rod-shaped liquid crystal compound or disk-shaped liquid crystal compound) in such a way that the orientation direction (slow axis direction) continuously changes at the interface. In the configuration described above, for example, when a second cholesterol-type liquid crystal layer formed using a rod-shaped liquid crystal compound is formed on a first layer that is a cholesterol-type liquid crystal layer formed using a disk-shaped liquid crystal compound, it is also possible to directly coat the coating liquid containing the rod-shaped liquid crystal compound onto the first layer, and align it continuously at the interface in the slow axis direction based on the orientation limiting force of the disk-shaped liquid crystal compound contained in the first layer.
[0219] The thickness of the optical laminate in the second embodiment of the present invention is preferably 30 μm or less, more preferably 15 μm or less.
[0220] There are no particular restrictions on the lower limit; for example, 1 μm or more is acceptable, and 5 μm or more is preferred.
[0221] The manufacturing method of the optical laminate according to the second embodiment of the present invention, and the laminated optical film using the optical laminate, will be described later.
[0222] [Third Implementation Method]
[0223] The optical laminate of the third embodiment of the present invention comprises a first layer, a second layer, and a third layer in sequence.
[0224] The first to the third layers mentioned above are all cholesterol-type liquid crystal layers.
[0225] The second layer mentioned above is a pitch gradient layer formed by the variation of the helical pitch in the film thickness direction.
[0226] All three layers mentioned above are light reflective.
[0227] The center wavelengths of the reflected light from the first to the third layers mentioned above are respectively within any one of the ranges of 430–480 nm, 520–620 nm, and 620–670 nm.
[0228] The sign of the film thickness retardation at 550 nm in the first layer is opposite to the sign of the film thickness retardation at 550 nm in the second layer.
[0229] The sign of the retardation in the thickness direction at a wavelength of 550 nm in the second layer is opposite to the sign of the retardation in the thickness direction at a wavelength of 550 nm in the third layer.
[0230] The optical laminate of the third embodiment of the present invention will be described with reference to the accompanying drawings. Figure 4 This is a schematic cross-sectional view showing an example of the structure of the optical laminate 13 of the third embodiment.
[0231] exist Figure 3 In the configuration shown, the optical laminate 13 consists of a first layer 27, a second layer 28, and a third layer 29 stacked sequentially, each satisfying the aforementioned necessary conditions. Furthermore, the sign of the Rth of the first layer 27 is opposite to that of the Rth of the second layer 28, and the sign of the Rth of the second layer 28 is opposite to that of the Rth of the third layer 29.
[0232] The optical laminate of the third embodiment of the present invention can be used in a reflective circular polarizer. It is believed that if the optical laminate has the above structure, the Rth values of the first layer and the second layer cancel each other out, and the Rth values of the second layer and the third layer cancel each other out, so the generation of ghosting can also be suppressed for incident light from the tilted direction.
[0233] The third embodiment of the present invention will now be described in detail.
[0234] [First to Third Floors]
[0235] The optical laminate of the third embodiment of the present invention comprises a first layer, a second layer and a third layer in sequence.
[0236] The first to third layers mentioned above are cholesterol-type liquid crystal layers with light reflectivity.
[0237] The aforementioned cholesterol-type liquid crystal layer refers to a layer formed by immobilizing a cholesterol-type liquid crystal phase with a liquid crystal compound. Such a cholesterol-type liquid crystal layer can be used in the cholesterol-type liquid crystal layers used in the first to fourth layers of the second embodiment.
[0238] The aforementioned cholesterol-type liquid crystal layer is preferably a cholesterol-type liquid crystal layer formed using rod-shaped liquid crystal compounds, or a cholesterol-type liquid crystal layer formed using disk-shaped liquid crystal compounds. In cholesterol-type liquid crystal layers formed using rod-shaped liquid crystal compounds, Rth tends to be a positive value, while in cholesterol-type liquid crystal layers formed using disk-shaped liquid crystal compounds, Rth tends to be a negative value.
[0239] Furthermore, the second layer is a pitch gradient layer formed by varying the helical pitch in the film thickness direction. The pitch gradient layer can be fabricated using known methods, for example, by referring to Japanese Patent Application Publication No. 2020-060627.
[0240] Because the helical pitch changes in the thickness direction within the pitch gradient layer, it can reflect light from multiple wavelength regions.
[0241] Furthermore, the center wavelengths of the reflected light from the first to the third layers are respectively within any one of the ranges of 430–480 nm, 520–620 nm, and 620–670 nm. Preferably, the center wavelengths of the reflected light from the first to the third layers are also different.
[0242] When the center wavelength of the reflected light is 430–480 nm, this layer can correspond to the blue light reflecting layer described in the first embodiment. In this case, the reflectivity at the center wavelength of the reflected light is preferably 40% or more and less than 50%.
[0243] When the center wavelength of the reflected light is 520–620 nm, this layer can correspond to the green or yellow light reflecting layer described in the first embodiment. In this case, the reflectivity at the center wavelength of the reflected light is preferably 40% or more and less than 50%.
[0244] When the center wavelength of the reflected light is 620–670 nm, this layer can correspond to the red light reflecting layer described in the first embodiment. In this case, the reflectivity at the center wavelength of the reflected light is preferably 40% or more and less than 50%.
[0245] The method for measuring reflectance is as described above.
[0246] The center wavelengths of the reflected light from the first to the third layers can be within any of the aforementioned wavelength ranges, but preferably the center wavelength of the reflected light from the first layer is in the range of 430–480 nm, the center wavelength of the other reflected light is in the range of 620–670 nm, the center wavelength of the reflected light from the second layer is in the range of 520–620 nm, and the center wavelength of the reflected light from the third layer is in the range of 620–670 nm.
[0247] That is, preferably, the first layer corresponds to the blue light reflective layer, the second layer corresponds to the green and yellow light reflective layers, and the third layer corresponds to the red light reflective layer. Since the second layer is a pitch gradient layer, it can perform the functions of the green and yellow light reflective layers in the first layer.
[0248] Furthermore, when the optical laminate with the stacking order described above is applied to the reflective circular polarizer described later, in the long-wavelength side reflective layer (e.g., red light reflective layer), the thickness of the reflective layer required to obtain sufficient reflectivity becomes thicker. At the point where the influence of the reflective layer's own Rth on the light transmitted through the reflective layer becomes greater, the reflective layer disposed on the light source side is preferably a short-wavelength side reflective layer (e.g., blue light reflective layer).
[0249] In the optical laminate of the third embodiment of the present invention, the sign of Rth at a wavelength of 550 nm in the first layer is opposite to the sign of Rth at a wavelength of 550 nm in the second layer, and the sign of Rth at a wavelength of 550 nm in the second layer is opposite to the sign of Rth at a wavelength of 550 nm in the third layer.
[0250] As described above, there are no particular limitations on the method of reversing the sign of Rth in the first and second layers, and reversing the sign of Rth in the second and third layers. However, as a way to establish such a relationship of Rth, for example, the following can be cited: the first layer is a cholesterol-type liquid crystal layer formed using a rod-shaped liquid crystal compound, the second layer is a cholesterol-type liquid crystal layer formed using a disc-shaped liquid crystal compound, and the third layer is a cholesterol-type liquid crystal layer formed using a rod-shaped liquid crystal compound. Furthermore, as a way to establish the Rth relationship as described above, for example, the following can also be cited: the first layer is a cholesterol-type liquid crystal layer formed using a disc-shaped liquid crystal compound, the second layer is a cholesterol-type liquid crystal layer formed using a rod-shaped liquid crystal compound, and the third layer is a cholesterol-type liquid crystal layer formed using a disc-shaped liquid crystal compound.
[0251] Furthermore, in the optical laminate of the third embodiment, the SRth described in the optical laminate of the first embodiment... i The absolute values are preferably within the ranges described above. Furthermore, in the definitions described above for the optical laminate of the first embodiment, n can be replaced with 3.
[0252] Specifically, SRth i The absolute values are preferably 0.3 μm or less, more preferably 0.2 μm or less, and even more preferably 0.1 μm or less.
[0253] It is believed that by SRth iWithin the aforementioned preferred range, the phase difference generated when transmitting through each reflective layer can be reduced, and the generation of ghosting can be further suppressed for incident light from the tilted direction.
[0254] In the optical laminate of the third embodiment of the present invention, the first to third layers can be laminated in direct contact with each other, or they can be laminated via other layers. There are no particular limitations on the other layers, but examples include bonding layers (e.g., adhesive layers, bonding layers, etc.), refractive index adjustment layers, resin films, positive C-plates, and alignment layers. Preferably, the first to third layers are laminated in direct contact with each other.
[0255] Furthermore, in the optical laminate of the third embodiment of the present invention, when the first to third layers are stacked in direct contact with each other, in order to reduce the refractive index difference, it is preferable to arrange the liquid crystal compound (rod-shaped liquid crystal compound or disk-shaped liquid crystal compound) in such a way that the orientation direction (slow axis direction) of the liquid crystal compound changes continuously at the interface. In the configuration described above, for example, when a second cholesterol-type liquid crystal layer formed using a rod-shaped liquid crystal compound is formed on a first layer that is a cholesterol-type liquid crystal layer formed using a disk-shaped liquid crystal compound, it is also possible to directly coat the coating liquid containing the rod-shaped liquid crystal compound onto the first layer, and align it continuously at the interface in the slow axis direction based on the orientation limiting force of the disk-shaped liquid crystal compound contained in the first layer.
[0256] The thickness of the optical laminate in the third embodiment of the present invention is preferably 30 μm or less, and more preferably 15 μm or less.
[0257] There are no particular restrictions on the lower limit; for example, 1 μm or more is acceptable, and 5 μm or more is preferred.
[0258] The manufacturing method of the optical laminate according to the third embodiment of the present invention, and the laminated optical film using the optical laminate, will be described later.
[0259] [Manufacturing method of optical laminates]
[0260] The optical laminate of the present invention (first embodiment, second embodiment and third embodiment) can be manufactured by known methods, and there are no particular limitations on the methods.
[0261] For example, as a method for manufacturing an optical laminate according to the first embodiment and the second embodiment, the following method can be described: after coating a composition containing a rod-shaped liquid crystal compound onto a substrate to form a cholesterol-type liquid crystal phase, the orientation state of the cholesterol-type liquid crystal phase is fixed to form a first cholesterol-type liquid crystal layer; after coating a composition containing a disk-shaped liquid crystal compound onto the first cholesterol-type liquid crystal layer to form a cholesterol-type liquid crystal phase, the orientation state of the cholesterol-type liquid crystal phase is fixed to form a second cholesterol-type liquid crystal layer; a third cholesterol-type liquid crystal layer is formed on the second cholesterol-type liquid crystal layer in the same manner as the first cholesterol-type liquid crystal layer; and a fourth cholesterol-type liquid crystal layer is formed on the third cholesterol-type liquid crystal layer in the same manner as the second cholesterol-type liquid crystal layer.
[0262] Furthermore, the first and third cholesterol-type liquid crystal layers correspond to reflective layer A in the first embodiment, and the second and fourth cholesterol-type liquid crystal layers correspond to reflective layer B in the first embodiment. Moreover, the first to fourth cholesterol-type liquid crystal layers correspond to the first to fourth layers in the second embodiment, respectively.
[0263] Furthermore, as a method for manufacturing an optical laminate according to the third embodiment, the following method can be cited: forming a first cholesterol-type liquid crystal layer on a substrate in the same manner as described above, forming a second cholesterol-type liquid crystal layer (pitch gradient layer) on the first cholesterol-type liquid crystal layer in the same manner as the first cholesterol-type liquid crystal layer, and forming a third cholesterol-type liquid crystal layer on the second cholesterol-type liquid crystal layer in the same manner as the first cholesterol-type liquid crystal layer.
[0264] Furthermore, the first to third cholesterol-type liquid crystal layers mentioned above correspond to the first to third layers of the second embodiment, respectively.
[0265] Furthermore, when using the optical laminate of the present invention in a reflective circular polarizer, if the reflective circular polarizer is stretched or molded, the reflection wavelength region of the reflective circular polarizer may sometimes shift towards the shorter wavelength side. Therefore, it is preferable to manufacture the optical laminate with a wavelength shift pre-assumed in the reflection wavelength region. For example, when using an optical laminate containing a layer formed by immobilizing a cholesterol-type liquid crystal phase as a reflective circular polarizer, the optical laminate is stretched by stretching or molding, which may cause the helical pitch of the cholesterol-type liquid crystal phase to become smaller. Therefore, the helical pitch of the cholesterol-type liquid crystal phase can be set to be larger. Furthermore, assuming the short-wavelength shift of the reflection wavelength region caused by stretching or molding, the optical laminate preferably has an infrared light reflecting layer with a reflectivity of 40% or more at a wavelength of 800 nm.
[0266] Furthermore, when the elongation ratio during stretching or forming is non-uniform in the plane, the optical laminate can be manufactured by selecting an appropriate reflection wavelength region at various positions within the plane of the optical laminate based on the wavelength displacement caused by stretching. That is, the reflection wavelength region can be different regions within the plane of the optical laminate. Moreover, it is also preferable to assume that the stretching ratio is different at various positions within the plane of the optical laminate and to pre-set the reflection wavelength region to be wider than the desired wavelength region.
[0267] The above describes a method of forming a cholesterol-type liquid crystal layer by directly coating the above composition onto each cholesterol-type liquid crystal layer. However, it is also possible to form the cholesterol-type liquid crystal layer by coating it onto different substrates and then stacking the cholesterol-type liquid crystal layer via an adhesive layer (e.g., a bonding layer, an adhesive layer).
[0268] As the adhesive used in the aforementioned adhesive layer, any commercially available adhesive can be used, but from the viewpoint of thinning and reducing surface roughness Ra, the thickness is preferably 25 μm or less, more preferably 15 μm or less, and most preferably 6 μm or less. Furthermore, the adhesive is preferably a substance that does not easily generate gas escape. In particular, in cases of stretching or molding, vacuum processes or heating processes are sometimes performed, and it is preferable that gas escape does not occur even under these conditions.
[0269] As the adhesive used in the above-mentioned adhesive layer, any commercially available adhesive can be used, such as epoxy resin-based adhesives or acrylic resin-based adhesives.
[0270] From the viewpoint of thinning and reducing the surface roughness Ra of the reflective circular polarizer using optical laminates, the thickness of the adhesive is preferably 25 μm or less, more preferably 5 μm or less, and most preferably 1 μm or less. Furthermore, from the viewpoint of thinning the adhesive layer and applying the adhesive to the adhesive body with a uniform thickness, the viscosity of the adhesive is preferably 300 cP or less, more preferably 100 cP or less.
[0271] Furthermore, when the adhesive has surface irregularities, from the viewpoint of reducing the surface roughness Ra of the reflective circular polarizer using the optical laminate, the adhesive or bonding agent can be selected with appropriate viscoelasticity or thickness to cover the surface irregularities of the bonded layers. From the viewpoint of covering the surface irregularities, the viscosity of the adhesive or bonding agent is preferably 50 cP or more. Furthermore, the thickness is preferably greater than the height of the surface irregularities.
[0272] One method for adjusting the viscosity of an adhesive is, for example, using an adhesive containing a solvent. In this case, the viscosity of the adhesive can be adjusted according to the ratio of the solvent. Furthermore, by applying the adhesive to the adhesive body and then allowing the solvent to dry, the thickness of the adhesive can be further reduced.
[0273] In reflective circular polarizers using optical laminates, from the viewpoint of reducing reflection at interfaces and suppressing the decrease in the polarization degree of transmitted light, the adhesives or bonding agents used in bonding the layers preferably have a small difference in refractive index compared to adjacent layers. Since cholesterol-type liquid crystal layers exhibit birefringence with different refractive indices along the fast and slow axes, the average refractive index n of the liquid crystal layer is defined as the sum of the refractive indices along the fast and slow axes divided by 2. ave When the refractive index of adjacent adhesive layers or bonding layers is different from that of n, ave The difference is preferably 0.075 or less, more preferably 0.05 or less, and even more preferably 0.025 or less. The refractive index of the adhesive or binder can be adjusted, for example, by mixing in microparticles of titanium oxide or microparticles of zirconium oxide.
[0274] Furthermore, the adhesive layer between each layer is preferably 100 nm or less thick. If the thickness of the adhesive layer is 100 nm or less, the light in the visible area is less likely to perceive the refractive index difference, thereby suppressing excess reflection. The thickness of the adhesive layer is more preferably 50 nm or less, and even more preferably 30 nm or less. As a method for forming an adhesive layer with a thickness of 100 nm or less, for example, a method of vapor-depositing a ceramic adhesive such as silicon oxide (SiOx layer) onto the bonding surface can be used. The bonding surface of the bonding component can be subjected to surface modification treatments such as plasma treatment, corona treatment, or saponification treatment before bonding, or a primer layer can be applied. Furthermore, in the case of multiple bonding surfaces, the type or thickness of the adhesive layer can be adjusted for each bonding surface. Specifically, for example, an adhesive layer with a thickness of 100 nm or less can be provided by the steps shown in (1) to (3) below.
[0275] (1) Laminating the laminates to a pseudo support made of a glass substrate.
[0276] (2) A SiOx layer with a thickness of less than 100 nm is formed on both the surface of the stacked layer and the surface of the stacked layer by means of vapor deposition or the like. Vapor deposition can be performed using SiOx powder as the vapor deposition source, for example, using a vapor deposition apparatus (model ULEYES) manufactured by ULVAC, Inc. Furthermore, it is preferable to pre-treat the surface of the formed SiOx layer with plasma.
[0277] (3) After the formed SiOx layers are bonded together, the dummy support is peeled off. Bonding is preferably carried out at a temperature of 120°C, for example.
[0278] The coating, bonding, or lamination of each layer can be done roll to roll or sheet by sheet.
[0279] From the perspective of improving productivity or reducing axial offset of each layer, roll-to-roll is preferred.
[0280] On the other hand, from the viewpoint of being suitable for small-batch, multi-variety production or being able to select special bonding methods such as the adhesive layer thickness of 100 nm or less as described above, the single-sheet method is preferred.
[0281] Furthermore, as methods for applying adhesive to the adhesive body, known methods such as roller coating, gravure printing, spin coating, wire rod coating, extrusion coating, direct gravure coating, reverse gravure coating, mold coating, spray coating, and inkjet coating can be cited.
[0282] The reflective circular polarizer using the optical laminate of the present invention may include a support and an alignment layer, etc., but the support and alignment layer may be a dummy support that is peeled off and removed during the fabrication of the laminated optical film described later. When using a dummy support, by peeling off and removing the dummy support after transferring the reflective circular polarizer to other laminates, the laminated optical film can be thinned. Furthermore, the phase difference possessed by the dummy support can eliminate the adverse effects on the polarization degree of the transmitted light, which is therefore preferable.
[0283] There are no particular restrictions on the type of support, but it is preferable to be transparent to visible light. For example, films such as cellulose acylates, polycarbonate, polysulfone, polyethersulfone, polyacrylate, polymethacrylate, cyclic polyolefins, polyolefins, polyamides, polystyrene, and polyesters can be used. Among these, cellulose acylate films, cyclic polyolefins, polyacrylates, or polymethacrylates are preferred. Furthermore, commercially available cellulose acetate films (e.g., "TD80U" or "Z-TAC" manufactured by FUJIFILMCorporation) can be used.
[0284] When the support is a quasi-support, from the viewpoint of preventing breakage during peeling, a support with high tear strength is preferred. For example, a polycarbonate or polyester-based film is preferred.
[0285] Furthermore, from the viewpoint of suppressing the adverse effects on the polarization of transmitted light, the support preferably has a small phase difference. Specifically, the value of Re at 550 nm is preferably 10 nm or less, and the absolute value of Rth is preferably 50 nm or less. Moreover, even if the support is used as the aforementioned pseudo-support, in the manufacturing process of the aforementioned stacked optical film, after quality inspection of the reflective circular polarizer or other stacked bodies, it is still preferable that the pseudo-support has a small phase difference.
[0286] Furthermore, to minimize the impact of various sensors that use near-infrared light as a light source, such as eye tracking, facial recognition, and iris authentication, which are assembled in optical systems such as virtual reality display devices or electronic viewfinders, the reflective circular polarizer used in the laminated optical film described later, which uses an optical laminate, preferably has transmissivity relative to near-infrared light.
[0287] [Laminated optical film]
[0288] The stacked optical film of the present invention comprises at least, in sequence, a reflective circular polarizer, a phase difference layer for converting circularly polarized light into linearly polarized light, and a linear polarizer.
[0289] As the aforementioned reflective circular polarizer, the optical laminate described above (first embodiment, second embodiment, or third embodiment) is used. The preferred embodiment of the optical laminate (first embodiment, second embodiment, or third embodiment) is as described above.
[0290] As a preferred example of the reflective circular polarizer of the present invention and the stacked optical film including the reflective circular polarizer, a virtual reality display device using the stacked optical film of the present invention can be cited to explain in detail the function of the stacked optical film of the present invention.
[0291] Figure 5 This is a schematic diagram of a virtual reality display device using the stacked optical film of the present invention. Figure 5 In the virtual reality display device shown, a stacked optical film 100 having a reflective circular polarizer using the aforementioned optical laminate, a semi-reflective mirror 300, a circular polarizer 400, and an image display panel 500 are arranged sequentially from the visual recognition side. Figure 5 As shown, light 1000 emitted from the image display panel 500 becomes circularly polarized light after passing through the circular polarizer 400, and then passes through the semi-reflective mirror 300. Next, it is incident on the stacked optical film 100 of the present invention from the side of the reflecting circular polarizer and is totally internally reflected, then reflected again by the semi-reflective mirror 300, and incident on the stacked optical film 100 again. At this time, by being reflected by the semi-reflective mirror, light 1000 becomes circularly polarized light with the opposite rotation direction to the circularly polarized light that was first incident on the stacked optical film 100. Therefore, light 1000 passes through the stacked optical film 100 and is visually recognized by the user. Furthermore, when light 1000 is reflected by the semi-reflective mirror 300, since the semi-reflective mirror is concave, the image displayed on the image display panel 500 is magnified, allowing the user to visually recognize the magnified virtual image. The above mechanism is called a reciprocating optical system or a retroreflective optical system, etc.
[0292] on the other hand, Figure 6 For the purpose of illustration Figure 5This diagram illustrates the ghosting phenomenon in a virtual reality display device. More specifically, it shows a situation where, when light 2000 first incident on the stacked optical film 100, it is not reflected but transmitted, resulting in light leakage. Figure 6 As shown, when light 2000 first incident on the stacked optical film 100, it is transmitted without being reflected, resulting in light leakage. Figure 6 It is known that users can visually recognize the unmagnified image. This image, referred to as ghosting, is required to be reduced.
[0293] Because the stacked optical film 100 of the present invention has a high degree of polarization, it can reduce the leakage (i.e., ghosting) of transmitted light when light first enters the stacked optical film 100.
[0294] Furthermore, since the stacked optical film 100 of the present invention also has a high degree of polarization for transmitted light, it can improve the transmittance when light is incident on the stacked optical film 100 for the second time, and can improve the brightness of the virtual image and thus suppress the color saturation of the virtual image.
[0295] like Figure 5 and Figure 6 As shown, the stacked optical film 100 is sometimes formed on curved surfaces such as lenses.
[0296] Because existing optical films, which are known as reflective circular polarizers and are formed by stacking reflective linear polarizers and a phase difference layer with a 1 / 4 wavelength phase difference, have optical axes such as a transmission axis, a reflection axis, and a slow axis, these optical axes deform during the extension and molding process into a curved shape, thereby reducing the polarization degree of the transmitted light. In contrast, in the stacked optical film 100 of the present invention, since the reflective circular polarizer (optical laminate) does not have an optical axis, it is difficult to cause a reduction in polarization degree due to extension or molding. Therefore, even when the stacked optical film 100 is molded into a curved shape, a reduction in polarization degree is less likely to occur.
[0297] An example of the layer structure of the stacked optical film 100 of the present invention is shown below. Figure 7 . Figure 7 The stacked optical film 100 shown includes, in sequence, an antireflective layer 101, a positive C-plate 102, a reflective circular polarizer 103, a positive C-plate 104, a phase retardation layer 105, and a linear polarizer 106. As described above, the reflective circular polarizer 103 uses the aforementioned optical laminate. Figure 7 The method shown uses an anti-reflective layer 101, a positive C-plate 102, and a positive C-plate 104, but some or all of them can be omitted in the above structure.
[0298] The stacked optical film of the present invention sequentially comprises a reflective circular polarizer 103, a phase retardation layer 105 for converting circularly polarized light into linearly polarized light, and a linear polarizer 106. Therefore, after the leakage light from the reflective circular polarizer 103 is converted into linearly polarized light, it can be absorbed by the linear polarizer. Thus, the polarization degree of the transmitted light can be improved. In addition, when the stacked optical film is stretched or shaped, the slow axis of the phase retardation layer or the absorption axis of the linear polarizer may be deformed. However, as described above, even if the reflective circular polarizer is stretched or shaped, it still has a high polarization degree, and the amount of leakage light from the reflective circular polarizer is small. Therefore, the increase in leakage light can be suppressed to a small amount.
[0299] Furthermore, the surface roughness Ra of the stacked optical film of the present invention is preferably 100 nm or less. A smaller Ra can improve image clarity, for example, when the stacked optical film is used in a virtual reality display device. The inventors hypothesize that if unevenness exists when light is reflected in the stacked optical film, it can lead to angular distortion of the reflected light, image distortion, or blurring. The Ra of the stacked optical film is preferably 50 nm or less, more preferably 30 nm or less, and particularly preferably 10 nm or less.
[0300] Furthermore, the stacked optical film of the present invention is fabricated by stacking multiple layers. According to the inventors' research, it has been found that when other layers are stacked on top of a layer with unevenness, unevenness amplification occurs. Therefore, in the stacked optical film of the present invention, it is preferable that the Ra values of all layers are small. The Ra values of each layer in the stacked optical film of the present invention are preferably 50 nm or less, more preferably 30 nm or less, and even more preferably 10 nm or less.
[0301] Furthermore, from the viewpoint of improving the image sharpness of the reflected image, a smaller Ra value for the reflecting circular polarizer is particularly preferred.
[0302] Surface roughness Ra can be measured, for example, using the non-contact surface-layer cross-sectional shape measurement system VertScan (manufactured by Ryoka Systems Inc.). Since VertScan is a surface shape measurement method that utilizes the phase of reflected light from the sample, in the case of measuring a reflective circular polarizer (the aforementioned optical laminate) composed of a reflective layer made of a fixed cholesterol-type liquid crystal phase, sometimes the reflected light from inside the thin film overlaps, making it impossible to accurately measure the surface shape. In this case, to increase the surface reflectivity and thus suppress reflections from within, a metal layer can be formed on the surface of the sample. As a method for forming a metal layer on the surface of the sample, sputtering can be used, for example. The sputtering material can be Au, Al, or Pt, etc.
[0303] The laminated optical film of the present invention preferably has a low number of point defects per unit area. Since the laminated optical film of the present invention is manufactured by stacking multiple layers, in order to reduce the overall number of point defects in the laminated optical film, it is preferable that the number of point defects in each layer is also low. Specifically, the number of point defects in each layer, per square meter, is preferably 20 or less, more preferably 10 or less, and even more preferably 1 or less. The overall number of point defects in the laminated optical film, per square meter, is preferably 100 or less, more preferably 50 or less, and even more preferably 5 or less.
[0304] Since point defects can reduce the polarization of transmitted light or reduce image sharpness, fewer point defects are preferred.
[0305] Point defects include foreign objects, scratches, dirt, film thickness variations, and poor alignment of liquid crystal compounds.
[0306] Furthermore, the number of point defects is preferably 100 μm or more, more preferably 30 μm or more, and most preferably 10 μm or more.
[0307] Furthermore, various sensors that use near-infrared light as a light source, such as eye tracking, facial recognition, and iris authentication, are sometimes assembled in optical systems such as virtual reality display devices or electronic viewfinders. In order to minimize the impact on the sensors, the stacked optical film of the present invention preferably has near-infrared light transmittance.
[0308] [Phase difference layer]
[0309] The retardation layer used in the stacked optical film of the present invention has the function of converting incident circularly polarized light into approximately linearly polarized light. For example, a retardation layer in which Re becomes approximately 1 / 4 of the wavelength at any wavelength in the visible region can be used. In this case, at a wavelength of 550 nm, the in-plane retardation Re (550) is preferably 120 nm to 150 nm, more preferably 125 nm to 145 nm, and even more preferably 135 nm to 140 nm.
[0310] Furthermore, a phase difference layer with Re of approximately 3 / 4 or 5 / 4 wavelength can also convert linearly polarized light into circularly polarized light, and is therefore preferred.
[0311] Furthermore, the phase difference layer used in the stacked optical film of the present invention preferably has anti-wavelength dispersion with respect to wavelength. Having anti-wavelength dispersion allows for the conversion of circularly polarized light into linearly polarized light over a wide wavelength range in the visible region, which is therefore preferable. Here, anti-wavelength dispersion with respect to wavelength means that as the wavelength increases, the phase difference value at that wavelength also increases.
[0312] A phase retardation layer with anti-wavelength dispersion can be fabricated, for example, by uniaxial stretching a polymer film such as a modified polycarbonate resin film with anti-wavelength dispersion, by referring to Japanese Patent Application Publication No. 2017-049574.
[0313] Furthermore, the phase retardation layer with anti-wavelength dispersion simply needs to have anti-wavelength dispersion. For example, as disclosed in Japanese Patent No. 06259925, it can be fabricated by stacking a phase retardation layer with a wavelength of approximately 1 / 4 wavelength (Re) and a phase retardation layer with a wavelength of approximately 1 / 2 wavelength, such that their slow axes are at an angle of approximately 60°. In this case, it is known that even if the 1 / 4 wavelength phase retardation layer and the 1 / 2 wavelength phase retardation layer are both of conventional wavelength dispersion (the phase difference value at that wavelength decreases as the wavelength increases), it is still possible to convert circularly polarized light into linearly polarized light over a wide wavelength range in the visible region, thus being considered to have substantial anti-wavelength dispersion. In this case, the stacked optical film of the present invention preferably comprises a reflective circular polarizer, a 1 / 4 wavelength phase retardation layer, a 1 / 2 wavelength phase retardation layer, and a linear polarizer in sequence.
[0314] Furthermore, the retardation layer used in the stacked optical film of the present invention preferably comprises a layer formed by immobilizing a uniformly oriented liquid crystal compound. For example, a layer in which a rod-shaped liquid crystal compound is uniformly oriented horizontally relative to the in-plane direction or a layer in which a disk-shaped liquid crystal compound is uniformly oriented vertically relative to the in-plane direction can be used. In addition, for example, by referring to Japanese Patent Application Publication No. 2020-084070, a retardation layer with anti-wavelength dispersion can be fabricated by uniformly oriented and immobilizing a rod-shaped liquid crystal compound with anti-wavelength dispersion.
[0315] Furthermore, the retardation layer used in the stacked optical film of the present invention preferably comprises a layer formed by immobilizing a liquid crystal compound that is twisted and oriented with the thickness direction as the helical axis. For example, as disclosed in Japanese Patent No. 05753922 or Japanese Patent No. 05960743, a retardation layer comprising a layer formed by immobilizing a rod-shaped liquid crystal compound or a disk-shaped liquid crystal compound that is twisted and oriented with the thickness direction as the helical axis can be used. In this case, the retardation layer can be considered to substantially have anti-wavelength dispersion, and is therefore preferred.
[0316] There is no particular limitation on the thickness of the phase retardation layer, but from the viewpoint of thinning, it is preferably 0.1 to 8 μm, and more preferably 0.3 to 5 μm.
[0317] The retardation layer of the present invention may include a support and an alignment layer, but the support and alignment layer may be a dummy support that is peeled off and removed during the fabrication of the laminated optical film. When using a dummy support, by transferring the retardation layer to other laminates and then peeling off and removing the dummy support, the laminated optical film can be made thinner. Furthermore, the retardation of the dummy support can eliminate the adverse effects on the polarization of the transmitted light, which is therefore preferable.
[0318] There are no particular restrictions on the type of support, but it is preferable to have a material that is transparent to visible light. For example, films made of cellulose acylates, polycarbonate, polysulfone, polyethersulfone, polyacrylate, polymethacrylate, cyclic polyolefins, polyolefins, polyamides, polystyrene, and polyesters can be used. Among these, cellulose acylate films, cyclic polyolefins, polyacrylates, or polymethacrylates are preferred. Furthermore, commercially available cellulose acetate films (e.g., "TD80U" or "Z-TAC" manufactured by FUJIFILMCorporation) can be used.
[0319] When the support is a quasi-support, from the viewpoint of preventing breakage during peeling, a support with high tear strength is preferred. For example, a polycarbonate or polyester-based film is preferred.
[0320] Furthermore, from the viewpoint of suppressing the adverse effects on the polarization degree of transmitted light, the support is preferably small in phase difference. Specifically, the value of Re is preferably 10 nm or less, and the absolute value of Rth is preferably 50 nm or less. Moreover, even if the support is used as the aforementioned dummy support, in the manufacturing process of the laminated optical film, after quality inspection of the phase difference layer or other laminates, it is still preferable that the dummy support has a small phase difference.
[0321] Furthermore, in order to minimize the impact of eye tracking, facial recognition, iris authentication, and other technologies assembled in optical systems such as virtual reality display devices or electronic viewfinders on various sensors that use near-infrared light as a light source, the phase retardation layer used in the stacked optical film of the present invention preferably has transmissivity relative to near-infrared light.
[0322] [Linear polarizer]
[0323] The linear polarizer used in the stacked optical film of the present invention is preferably an absorption-type linear polarizer. An absorption-type linear polarizer absorbs linearly polarized light along the absorption axis of the incident light and transmits linearly polarized light along the transmission axis. As the linear polarizer, a general polarizer can be used; for example, a polarizer that orients a dichroic substance by dyeing polyvinyl alcohol or other polymer resins with iodine and then stretching it, or a polarizer that orients a dichroic substance by utilizing the orientation of a liquid crystal compound. From the viewpoint of availability or improving the degree of polarization, a polarizer that dyes polyvinyl alcohol with iodine and then stretches it is preferred.
[0324] Regarding the thickness of the linear polarizer, it is preferably 10 μm or less, more preferably 7 μm or less, and even more preferably 5 μm or less. If the linear polarizer is thin, cracks or breaks in the thin film can be prevented when stretching or forming laminated optical films.
[0325] Furthermore, the transmittance of the single plate of the linear polarizer is preferably 40% or more, more preferably 42% or more. The degree of polarization is preferably 90% or more, more preferably 95% or more, and even more preferably 99% or more. In this specification, the transmittance and degree of polarization of the single plate of the linear polarizer are measured using an automatic polarizing film measuring device: VAP-7070 (manufactured by JASCO Corporation).
[0326] Furthermore, the direction of the transmission axis of the linear polarizer is preferably aligned with the direction of the polarization axis of the light that is converted into linearly polarized light through the retardation layer. For example, when the retardation layer is a layer with a phase difference of 1 / 4 wavelength, the angle between the transmission axis of the linear polarizer and the slow axis of the retardation layer is preferably about 45°.
[0327] The linear polarizer used in the stacked optical film of the present invention is preferably a light-absorbing anisotropic layer containing a liquid crystal compound and a dichroic material. Linear polarizers containing liquid crystal compounds and dichroic materials can be made thinner, and are less prone to cracking or breakage even when stretched or molded, therefore they are preferred. The thickness of the light-absorbing anisotropic layer is not particularly limited, but from the viewpoint of thinning, it is preferably 0.1 to 8 μm, more preferably 0.3 to 5 μm.
[0328] A linear polarizer comprising a liquid crystal compound and a dichroic material can be manufactured, for example, with reference to Japanese Patent Application Publication No. 2020-023153. From the viewpoint of improving the polarization degree of the linear polarizer, the orientation degree of the dichroic material in the light absorption anisotropy layer is preferably 0.95 or higher, and more preferably 0.97 or higher.
[0329] The liquid crystal compound contained in the composition for forming the light-absorbing anisotropic layer is preferably a liquid crystal compound that does not exhibit dichroism in the visible region.
[0330] As a liquid crystal compound, either a low-molecular-weight liquid crystal compound or a high-molecular-weight liquid crystal compound can be used. Here, "low-molecular-weight liquid crystal compound" refers to a liquid crystal compound that does not have repeating units in its chemical structure. Here, "high-molecular-weight liquid crystal compound" refers to a liquid crystal compound that has repeating units in its chemical structure.
[0331] Examples of polymeric liquid crystal compounds include, for instance, the thermotropic liquid crystal polymer described in Japanese Patent Application Publication No. 2011-237513. Furthermore, the polymeric liquid crystal compound preferably has crosslinking groups (e.g., acryloyl and methacryloyl groups) at its ends.
[0332] Liquid crystal compounds can be used alone or in combination with two or more. It is also preferred to use a combination of high molecular weight liquid crystal compounds and low molecular weight liquid crystal compounds.
[0333] Relative to 100 parts by mass of the dichroic substance in this composition, the content of the liquid crystal compound is preferably 25 to 2000 parts by mass, more preferably 33 to 1000 parts by mass, and even more preferably 50 to 500 parts by mass. With the liquid crystal compound content within the above range, the orientation degree of the polarizer is further improved.
[0334] There are no particular limitations on the dichroic substances contained in the composition for forming the light-absorbing anisotropic layer. Examples include visible light absorbing substances (dichroic pigments), ultraviolet light absorbing substances, infrared light absorbing substances, nonlinear optical substances, carbon nanotubes, etc. Existing known dichroic substances (dichroic pigments) can be used.
[0335] In this invention, two or more dichroic materials may be used together. For example, from the viewpoint of obtaining a high degree of polarization over a wider wavelength range, it is preferable to use at least one dichroic material having a maximum absorption wavelength in the wavelength range of 370 to 550 nm and at least one dichroic material having a maximum absorption wavelength in the wavelength range of 500 to 700 nm.
[0336] In the case where the linear polarizer of the present invention is composed of a light-absorbing anisotropic layer containing a liquid crystal compound and a dichroic material, the linear polarizer may include a support and an alignment layer, etc. However, the support and alignment layer may also be a dummy support that is peeled off and removed during the fabrication of the laminated optical film. When using a dummy support, by transferring the light-absorbing anisotropic layer to other laminates and then peeling off and removing the dummy support, the laminated optical film can be made thinner. Furthermore, the phase difference possessed by the dummy support can eliminate the adverse effects on the polarization degree of the transmitted light, which is therefore preferable.
[0337] There are no particular restrictions on the type of support, but it is preferable that it be transparent to visible light. For example, the same support used as the one used as the retardation layer described above can be used. The preferred method for the support used in the linear polarizer is the same as the preferred method for the support used as the retardation layer described above.
[0338] Furthermore, in order to minimize the impact of eye tracking, facial recognition, iris authentication, and other optical systems assembled in virtual reality display devices or electronic viewfinders on various sensors that use near-infrared light as a light source, the linear polarizer used in the stacked optical film of the present invention preferably has transmissivity relative to near-infrared light.
[0339] [Other functional layers]
[0340] In addition to the reflective circular polarizer, phase difference layer, and linear polarizer, the stacked optical film of the present invention may also have other functional layers.
[0341] Furthermore, in order to minimize the impact of eye tracking, facial recognition, iris authentication, and other technologies assembled in optical systems such as virtual reality display devices or electronic viewfinders on various sensors that use near-infrared light as a light source, other functional layers are preferably transmissive to near-infrared light.
[0342] <Positive C Board>
[0343] The laminated optical film of the present invention preferably has a positive C-plate. Here, a positive C-plate refers to a phase retardation layer where Re is substantially zero and Rth has a negative value. The positive C-plate is obtained, for example, by vertically aligning a rod-shaped liquid crystal compound. Detailed descriptions of the manufacturing method of the positive C-plate can be found, for example, in Japanese Patent Application Publication Nos. 2017-187732, 2016-053709, and 2015-200861.
[0344] The positive C-plate functions as an optical compensation layer, which increases the polarization of transmitted light relative to light incident at an angle. Multiple positive C-plates can be placed at any position on the stacked optical films.
[0345] The positive C-plate can be adjacent to the reflective circular polarizer, or it can be disposed inside the reflective circular polarizer. As a reflective circular polarizer, for example, when a reflective layer formed by immobilizing a cholesterol-type liquid crystal phase containing a rod-shaped liquid crystal compound is used, the reflective layer has a positive Rth. In this case, when light is incident from an oblique direction relative to the reflective circular polarizer, the polarization state of the reflected and transmitted light changes due to the effect of Rth, and sometimes the polarization degree of the transmitted light decreases. If a positive C-plate is disposed inside or near the reflective circular polarizer, the change in the polarization state of the obliquely incident light can be further suppressed, and the decrease in the polarization degree of the transmitted light can be further suppressed. As a result, ghosting can be further suppressed, which is therefore preferable. According to the inventors' research, the positive C-plate is preferably disposed on the side opposite to the green reflective layer relative to the blue light reflective layer, but it can also be disposed in other positions. In this case, the Re of the positive C-plate is preferably about 10 nm or less, and the Rth is preferably -600 to -100 nm, more preferably -400 to -200 nm.
[0346] Furthermore, the positive C-plate can be adjacent to the retardation layer, or disposed within the retardation layer. As the retardation layer, for example, when a layer formed by immobilizing a rod-shaped liquid crystal compound is used, the retardation layer has a positive Rth. In this case, when light is incident from an oblique direction relative to the retardation layer, the polarization state of the transmitted light changes due to the effect of Rth, and sometimes the degree of polarization of the transmitted light decreases. If a positive C-plate is disposed inside or near the retardation layer, the change in the polarization state of the obliquely incident light can be suppressed, and the decrease in the degree of polarization of the transmitted light can also be suppressed, which is therefore preferable. According to the inventors' research, the positive C-plate is preferably disposed on the side opposite to the linear polarizer relative to the retardation layer, but it can also be disposed in other positions. In this case, the Re of the positive C-plate is preferably about 10 nm or less, and the Rth is preferably -90 to -40 nm.
[0347] <Anti-reflective layer>
[0348] The laminated optical film of the present invention preferably has an anti-reflective layer on its surface. The laminated optical film of the present invention has the function of reflecting specific circularly polarized light and transmitting circularly polarized light orthogonal to it; however, reflections on the surface of the laminated optical film often include reflections of unexpectedly polarized light, which can sometimes reduce the polarization degree of the transmitted light. Therefore, the laminated optical film preferably has an anti-reflective layer on its surface. The anti-reflective layer may be disposed on only one surface of the laminated optical film or on both surfaces.
[0349] There are no particular restrictions on the type of anti-reflective layer, but from the viewpoint of further reducing reflectivity, moth-eye film or AR (Anti-Reflective) film is preferred. Known films can be used for moth-eye film and AR film.
[0350] Furthermore, when stretching or molding the laminated optical film, high anti-reflective performance can be maintained even if the film thickness changes due to stretching, making a moth-eye film preferable. In addition, the anti-reflective layer includes a support, and from the viewpoint of ease of stretching or molding, the peak temperature (Tg) of the support is preferably below 170°C, and more preferably below 130°C. Specifically, for example, a PMMA film is preferred.
[0351] <Second phase difference layer>
[0352] The stacked optical film of the present invention preferably also has a second phase retardation layer. For example, it may also sequentially include a reflective circular polarizer, a phase retardation layer, a linear polarizer, and a second phase retardation layer.
[0353] The second phase retardation layer preferably converts linearly polarized light into circularly polarized light; for example, it is preferably a phase retardation layer with a Re wavelength of 1 / 4 of the wavelength. The reasons for this will be explained below.
[0354] Light incident on the stacked optical film from the reflective circular polarizer side, and transmitted through the reflective circular polarizer, phase difference layer, and linear polarizer, becomes linearly polarized. A portion of this light is reflected from the outermost surface on the linear polarizer side and then exits again from the surface on the reflective circular polarizer side. This excess reflected light can be a major cause of reduced polarization of the reflected light, and therefore should be minimized. Thus, methods for stacking anti-reflective layers exist to suppress reflection from the outermost surface on the linear polarizer side. However, if the stacked optical film is bonded to a medium such as glass or plastic, even with an anti-reflective layer on the bonding surface of the stacked optical film, reflection from the medium surface cannot be suppressed, making it difficult to achieve an anti-reflective effect.
[0355] On the other hand, when a second phase difference layer is provided to convert linearly polarized light into circularly polarized light, the light reaching the outermost surface of the linear polarizer becomes circularly polarized light, and upon reflection at the outermost surface of the medium, it is converted into orthogonally circularly polarized light. Then, when it passes through the second phase difference layer again and reaches the linear polarizer, the light becomes linearly polarized light aligned with the absorption axis of the linear polarizer and is absorbed by it. Therefore, unnecessary reflections can be prevented.
[0356] From the viewpoint of more effectively suppressing excess reflections, the second phase difference layer preferably has substantially anti-wavelength dispersion.
[0357] <Support>
[0358] The laminated optical film of the present invention may also have a support. The support can be disposed in any location; for example, in the case of a thin film used for transfer from a pseudo-support in a reflective circular polarizer, retardation layer, or linear polarizer, the support can be used as the transfer destination.
[0359] There are no particular restrictions on the type of support, but it is preferable to have a material that is transparent to visible light. For example, films made of cellulose acylates, polycarbonate, polysulfone, polyethersulfone, polyacrylate, polymethacrylate, cyclic polyolefins, polyolefins, polyamides, polystyrene, and polyesters can be used. Among these, cellulose acylate films, cyclic polyolefins, polyacrylates, or polymethacrylates are preferred. Furthermore, commercially available cellulose acetate films (e.g., "TD80U" or "Z-TAC" manufactured by FUJIFILMCorporation) can be used.
[0360] Furthermore, from the viewpoint of suppressing the adverse effects on the polarization of transmitted light and facilitating optical inspection of stacked optical films, the support preferably has a small phase difference. Specifically, the value of Re is preferably 10 nm or less, and the absolute value of Rth is preferably 50 nm or less.
[0361] When the laminated optical film of the present invention is stretched or molded, the peak temperature of tanδ of the support is preferably 170°C or lower. From the viewpoint of being able to be molded at low temperatures, the peak temperature of tanδ is preferably 150°C or lower, and more preferably 130°C or lower.
[0362] Here, the method for determining tanδ is described. Using a dynamic viscoelasticity measuring apparatus (IT Keisoku Seigyo Co., Ltd. DVA-200), film samples that had been conditioned for more than 2 hours at a temperature of 25°C and a humidity of 60% Rh atmosphere were measured under the following conditions, and the values were used to determine the value of tanδ (=E” / E’).
[0363] Device: DVA-200 manufactured by IT Keisoku Seigyo Co., Ltd.
[0364] Sample size: 5mm, length 50mm (gap 20mm)
[0365] Measurement conditions: Tensile mode
[0366] Measurement temperature: -150℃~220℃
[0367] Heating rate: 5℃ / min
[0368] Frequency: 1Hz
[0369] In addition, in optical applications, stretched resin substrates are often used, and the peak temperature of tanδ is often high due to stretching. For example, the peak temperature of tanδ for TAC (triacetyl cellulose) substrates (TG40, manufactured by FUJIFIL M Corporation) is above 180°C.
[0370] There are no particular limitations on the support for which the tanδ peak temperature is below 170°C, and various resin substrates can be used. Examples include polyolefins such as polyethylene, polypropylene, and norbornene polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; acrylic resins such as polymethacrylate and polyacrylate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyetherketone; polyphenylene sulfide; and polyphenylene oxide. Among these, cyclic olefin resins, polyethylene terephthalate, or acrylic resins are preferred from the viewpoint of being readily available on the market or having excellent transparency; cyclic olefin resins or polymethacrylate are particularly preferred.
[0371] Commercially available resin substrates include TECHNOLLOY S001G, TECHNOLLOY S014G, TECHNOLLOY S000, TECHNOLLOY C001, TECHNOLLOY C000 (Copyright Sumika Acryl Co., Ltd.), Lumirror U type, Lumirror FX10, Lumirror SF20 (TORAY INDUSTRIES, INC.), HK-53A (HYNT.), TEFLEX FT3 (Teijin DuPont Films Japan Ltd.), ESSINA and SCA40 (SEKISUICHEMICAL CO.,LTD.), ZEONOR film (ZEON CORPORATION.), and ARTON film (JSR Corporation).
[0372] The thickness of the support is not particularly limited, but is preferably 5 to 300 μm, more preferably 5 to 100 μm, and even more preferably 5 to 30 μm.
[0373] Furthermore, the laminated optical film may have layers other than those described above. Examples of such layers include adhesive layers formed by adhesives described later, adhesive layers formed by adhesives described later, and refractive index adjustment layers.
[0374] Furthermore, a refractive index adjustment layer, where the difference in refractive index between the fast axis and the slow axis is smaller than that of the reflective circular polarizer, can be provided between the reflective circular polarizer and the adhesive, or between the reflective circular polarizer and the adhesive. In this case, the refractive index adjustment layer preferably has a layer formed by fixing the orientation state of the cholesterol-type liquid crystal. By having a refractive index adjustment layer, interface reflection can be further suppressed, and ghosting can be further suppressed. Moreover, the average refractive index of the refractive index adjustment layer is more preferably smaller than the average refractive index of the reflective circular polarizer. Furthermore, the center wavelength of the reflected light from the refractive index adjustment layer can be less than 430 nm or greater than 670 nm, more preferably less than 430 nm.
[0375] [Adhesion methods for each layer]
[0376] The laminated optical film of the present invention is a laminate composed of multiple layers. The layers can be bonded by any bonding method, for example, adhesives or bonding agents can be used.
[0377] As the adhesive, any commercially available adhesive can be used, but from the viewpoint of thinning and reducing the surface roughness Ra of the laminated optical film, the thickness is preferably 25 μm or less, more preferably 15 μm or less, and most preferably 6 μm or less. Furthermore, the adhesive is preferably a material that does not easily generate gas escape. In particular, in cases of stretching or molding, vacuum processes or heating processes are sometimes performed, and it is preferable that gas escape does not occur even under these conditions.
[0378] As an adhesive, any commercially available adhesive can be used, such as epoxy resin-based adhesives or acrylic resin-based adhesives.
[0379] From the viewpoint of thinning and reducing the surface roughness Ra of the laminated optical film, the thickness of the adhesive is preferably 25 μm or less, more preferably 5 μm or less, and most preferably 1 μm or less. Furthermore, regarding the adhesive, from the viewpoint of thinning the adhesive layer and applying the adhesive with a uniform thickness relative to the adhesive body, a viscosity of 300 cP or less is preferred, more preferably 100 cP or less, and even more preferably 10 cP or less.
[0380] Furthermore, when the adhesive has an uneven surface, from the viewpoint of reducing the surface roughness Ra of the laminated optical film, the adhesive or bonding agent can be selected with appropriate viscoelasticity or thickness to cover the surface unevenness of the bonded layers. From the viewpoint of covering the surface unevenness, the viscosity of the adhesive or bonding agent is preferably 50 cP or more. Furthermore, the thickness is preferably greater than the height of the surface unevenness.
[0381] One method for adjusting the viscosity of an adhesive is, for example, using an adhesive containing a solvent. In this case, the viscosity of the adhesive can be adjusted according to the ratio of the solvent. Furthermore, by applying the adhesive to the adhesive body and then allowing the solvent to dry, the thickness of the adhesive can be further reduced.
[0382] In a stacked optical film, from the viewpoint of reducing excess reflection and suppressing the reduction of the polarization degree of transmitted and reflected light, the adhesive or bonding agent used in bonding each layer is preferably small in refractive index difference with adjacent layers. Specifically, the refractive index difference between adjacent layers is preferably 0.1 or less, more preferably 0.05 or less, and even more preferably 0.01 or less. The refractive index of the adhesive or bonding agent can be adjusted, for example, by mixing in microparticles of titanium dioxide or zirconium oxide.
[0383] Furthermore, while reflective circular polarizers, retardation layers, and linear polarizers sometimes exhibit in-plane refractive index anisotropy, the refractive index difference with adjacent layers is preferably 0.05 or less in all directions within the plane. Therefore, adhesives or bonding agents can also exhibit in-plane refractive index anisotropy.
[0384] Furthermore, the adhesive layer between each layer is preferably 100 nm or less thick. If the thickness of the adhesive layer is 100 nm or less, the light in the visible region is less likely to perceive the refractive index difference, thereby suppressing reflection at the interface. The thickness of the adhesive layer is more preferably 50 nm or less. As a method for forming an adhesive layer with a thickness of 100 nm or less, for example, a method of vapor-depositing a ceramic adhesive such as silicon oxide (SiOx layer) onto the bonding surface can be used. The bonding surface of the bonding component can be subjected to surface modification treatments such as plasma treatment, corona treatment, or saponification treatment before bonding, or a primer layer can be applied. Furthermore, in the case of multiple bonding surfaces, the type or thickness of the adhesive layer can be adjusted for each bonding surface. Specifically, for example, an adhesive layer with a thickness of 100 nm or less can be provided by the steps shown in (1) to (3) below.
[0385] (1) Laminating the laminates to a pseudo support made of a glass substrate.
[0386] (2) A SiOx layer with a thickness of less than 100 nm is formed on both the surface of the stacked layer and the surface of the stacked layer by means of vapor deposition or the like. Vapor deposition can be performed using SiOx powder as the vapor deposition source, for example, using a vapor deposition apparatus (model ULEYES) manufactured by ULVAC, Inc. Furthermore, it is preferable to pre-treat the surface of the formed SiOx layer with plasma.
[0387] (3) After the formed SiOx layers are bonded together, the dummy support is peeled off. Bonding is preferably carried out at a temperature of 120°C, for example.
[0388] Coating, bonding, or laminating of each layer can be done roll-to-roll or sheet-by-sheet. From the viewpoint of improving productivity or reducing axial misalignment of each layer, roll-to-roll is preferred.
[0389] On the other hand, from the viewpoint of being suitable for small-batch, multi-variety production or being able to select special bonding methods such as the adhesive layer thickness of 100 nm or less as described above, the single-sheet method is preferred.
[0390] Furthermore, as methods for applying adhesive to the adhesive body, known methods such as roller coating, gravure printing, spin coating, wire rod coating, extrusion coating, direct gravure coating, reverse gravure coating, mold coating, spray coating, and inkjet coating can be cited.
[0391] [Direct coating of each layer]
[0392] Preferably, there is no adhesive layer between the layers of the stacked optical film of the present invention. During layer formation, the adhesive layer can be eliminated by directly coating adjacent layers that have already been formed. Furthermore, when one or two layers in adjacent layers are layers containing a liquid crystal compound, in order to reduce the refractive index difference in all in-plane directions, it is preferable that the orientation direction of the liquid crystal compound changes continuously at the interface. For example, it is also possible to directly coat a phase retardation layer containing a liquid crystal compound into a linear polarizer containing a liquid crystal compound and a dichroic material, and align the liquid crystal compound of the phase retardation layer continuously at the interface by the orientation constraint force of the liquid crystal compound based on the linear polarizer.
[0393] [Stacking order of each layer]
[0394] The laminated optical film of the present invention is composed of multiple layers, and there are no particular restrictions on the order of the lamination process; the order can be chosen arbitrarily.
[0395] For example, when transferring a functional layer from a thin film consisting of a pseudo-support and a functional layer, wrinkles or cracks during transfer can be prevented by adjusting the stacking order so that the thickness of the film at the transfer destination is 10 μm or more.
[0396] Furthermore, from the viewpoint of reducing the surface roughness Ra of the stacked optical film, when other layers are stacked on top of layers with large surface irregularities, since the surface irregularities may be further amplified, it is preferable to start stacking from layers with smaller surface roughness Ra.
[0397] Furthermore, from the perspective of quality evaluation in the fabrication process of stacked optical films, the order of stacking can also be selected. For example, after stacking layers other than the reflective circular polarizer and performing quality evaluation based on the transmission optical system, the reflective circular polarizer can be stacked and quality evaluation based on the reflection optical system can be performed.
[0398] Furthermore, from the perspective of improving the manufacturing yield of laminated optical films or reducing costs, the order of lamination can also be selected.
[0399] [Application of the stacked optical film of the present invention]
[0400] For example, as described in Patent Documents 4-5, the laminated optical film of the present invention can be used as a reflective polarizer assembled in automotive rearview mirrors, virtual reality display devices, and electronic viewfinders. In particular, the laminated optical film of the present invention is very useful from the viewpoint of improving the clarity of the displayed image in virtual reality display devices or electronic viewfinders that have a reciprocating optical system in which light is reflected and retrievaled between a reflective polarizer and a semi-reflective mirror. Furthermore, virtual reality display devices or electronic viewfinders with reciprocating optical systems sometimes have optical films such as absorptive polarizers or circular polarizers in addition to reflective polarizers; however, by also using a portion of the components or bonding method used in the laminated optical film of the present invention in optical films other than the aforementioned reflective polarizers, the clarity of the displayed image can be further improved.
[0401] Example
[0402] The following examples illustrate the features of the present invention in further detail. Furthermore, the materials, amounts, proportions, processing contents, and processing steps shown below can be appropriately modified as long as they do not depart from the spirit of the present invention. Moreover, structures other than those shown below can be used as long as they do not depart from the main spirit of the present invention.
[0403] [Preparation of coating solution for reflective layer]
[0404] <Reflective layer coating liquid R-1>
[0405] A coating solution R-1 for a reflective layer was prepared by stirring and dissolving the composition shown below in a container at a temperature maintained at 70°C. Here, R indicates a coating solution using a rod-shaped liquid crystal compound.
[0406]
[0407]
[0408] Mixture of rod-shaped liquid crystal compounds
[0409] [Chemical Formula 1]
[0410]
[0411] In the above mixture, the values are by mass%. Furthermore, R represents a group bonded by oxygen atoms. Moreover, the average molar absorptivity of the above rod-shaped liquid crystal at wavelengths of 300–400 nm is 140 / mol·cm.
[0412] Chiral reagent A
[0413] [Chemical Formula 2]
[0414]
[0415] Surfactant F1
[0416] [Chemical Formula 3]
[0417]
[0418] Surfactant F2
[0419] [Chemical Formula 4]
[0420]
[0421] Photopolymerization initiator B
[0422] [Chemical Formula 5]
[0423]
[0424] Chiral reagent A is a chiral reagent whose helical torsional power (HTP) is reduced by light.
[0425] <Reflective layer coating solutions R-2 to R-6, R-11 to R-17>
[0426] The amount of chiral reagent A added was changed to that shown in Table 1 below, and otherwise prepared in the same manner as the coating solution R-1 for the reflective layer.
[0427] <Reflective coating liquid R-7>
[0428] Chiral reagent A was replaced with chiral reagent B, as indicated in the following description, and otherwise prepared in the same manner as the coating solution R-1 for the reflective layer. The synthesis method of chiral reagent B is shown below.
[0429] (Synthesis of Intermediate 1)
[0430] 55.0 g of (S)-naphthol (manufactured by Tokyo Chemical Industry Co., Ltd.) and 485 g of butyl acetate (manufactured by Wako Pure Chemical, Ltd.) were added to a 1 L three-necked flask and dissolved. The solution was then cooled with ice water. 82.9 g of bromine (manufactured by Wako Pure Chemical, Ltd.) was added dropwise at 0–10 °C, and the mixture was stirred directly at 0–10 °C for 3 hours. Next, sodium bisulfite solution (18.28 g of sodium bisulfite (manufactured by Wako Pure Chemical, Ltd.) and 275 mL of water) was added to the resulting reaction solution while maintaining a temperature below 10 °C. The mixture was then heated to room temperature and the aqueous layer was removed. The organic layer was washed sequentially with 275 mL of water and then with sodium bicarbonate solution (11.0 g of sodium bicarbonate (manufactured by Wako Pure Chemical, Ltd.) and 275 mL of water). After drying the cleaned solution with magnesium sulfate, the solvent was distilled under reduced pressure until the volume was 160g, and then transferred to a three-necked flask.
[0431] Next, 66.2 g of DMF (N,N-dimethylformamide, manufactured by Wako Pure Chemical, Ltd.), 79.7 g of potassium carbonate (manufactured by NIPPON SODA CO.,LTD.), and 43.4 g of dibromomethane (manufactured by Wako Pure Chemical, Ltd.) were added to the three-necked flask. The mixture was heated to 90°C and stirred directly at 90–95°C for 8 hours. After cooling the reaction solution to room temperature, the solid was filtered while being washed with 170 mL of ethyl acetate (manufactured by Wako Pure Chemical, Ltd.). The filtered solid solution was concentrated under reduced pressure to a volume of 215 g, and then 550 mL of methanol (manufactured by Wako Pure Chemical, Ltd.) was added at 45–50°C to induce crystallization. After cooling the solution to 0–5°C, the crystals were filtered off and washed with 220 mL of methanol. The obtained crude crystals were suspended in 550 mL of methanol and stirred at 0–5 °C for 30 minutes. The crystals were then filtered off by vacuum filtration and washed with 220 mL of methanol. The obtained crystals were dried under reduced pressure at 55 °C for 24 hours to obtain intermediate 1 (63.1 g, yield: 72%).
[0432] (Synthesis of intermediate 2)
[0433] 13.8 g of intermediate 1, 46.8 g of butyl acrylate (manufactured by Wako Pure Chemical, Ltd.), 42.2 g of potassium carbonate (manufactured by NIPPON SODA CO.,LTD.), 39.2 g of tetrabutylammonium bromide (manufactured by Wako Pure Chemical, Ltd.), 0.19 g of 2,2,6,6-tetramethylpiperidine 1-oxo radical (TEMPO, manufactured by Wako Pure Chemical, Ltd.), and 47.0 g of DMF (N,N-dimethylformamide, manufactured by Wako Pure Chemical, Ltd.) were added to a 1 L three-necked flask, bubbled with nitrogen for 2 hours, and degassed. Next, 12.3 g of triethylamine (manufactured by Wako Pure Chemical, Ltd.), 0.41 g of palladium acetate (manufactured by Wako Pure Chemical, Ltd.), and 11 g of DMF were added. The mixture was stirred at room temperature for 1 hour under nitrogen flow, followed by further stirring at an internal temperature of 80–85°C for another hour. While maintaining the internal temperature at 80–85°C, a solution of 141.8 g of intermediate (prepared by bubbling under nitrogen for 2 hours) dissolved in 127.0 g of DMF was added dropwise to the reaction mixture, and the mixture was stirred at 90–95°C for 1 hour. After the reaction was complete, the mixture was cooled to room temperature, and 420 mL of toluene (manufactured by Wako Pure Chemical, Ltd.) was added. The solids were removed by diatomaceous earth filtration, followed by washing with 305 mL of toluene. The solution after filtering the solid was washed twice with a mixture of 77.8 g sodium chloride, 11.84 g concentrated hydrochloric acid, and 440 mL water, followed by washing with a mixture of 103 g sodium chloride and 415 mL water. The washed solution was dried with magnesium sulfate, and then 110 g silica gel (Wakogel C200, manufactured by Wako Pure Chemical, Ltd.) was added. After stirring for 1 hour, the solution was washed with 490 mL toluene while being filtered through diatomaceous earth to remove the solid. 0.19 g TEMPO was added to the solution after filtering the solid, and the solvent was distilled under reduced pressure. The volume was reduced to 100 mL, transferred to a three-necked flask, and 40 mL toluene was added. The temperature was raised to 60 °C. At 50–60 °C, 355 mL methanol (manufactured by Wako Pure Chemical, Ltd.) was added dropwise to the solution, and then the temperature was lowered to 45 °C to allow crystals to precipitate. After cooling the solution to 0–5°C for 2 hours, the crystals were filtered off and washed sequentially with a mixed solvent of 72 mL toluene, 290 mL methanol, and 360 mL methanol. The resulting crystals were dried under blast air at 40°C for 24 hours to obtain intermediate 2 (47.6 g, yield: 71%).
[0434] (Synthesis of chiral reagent B)
[0435] In a 2L three-necked flask, 245g of intermediate was dissolved in 900mL of ethyl acetate. At room temperature, 27.8g of a 20% sodium ethoxide solution (manufactured by NIPPON SODA CO.,LTD.) was added dropwise to this solution, and the mixture was stirred at 20–25°C for 2 hours. In another 2L three-necked flask, a mixture of 41.4g of sodium chloride, 8.97g of concentrated hydrochloric acid, and 240mL of water was prepared. The mixture was cooled to below 15°C, and while maintaining an internal temperature below 30°C, the previous reaction solution was added. 45mL of ethyl acetate was then added, stirred, allowed to stand, and the aqueous layer was removed. The resulting organic layer was washed twice, sequentially, with a mixture of 54g of sodium chloride and 215mL of water, a mixture of 5.1g of sodium bicarbonate, 41g of sodium chloride, and 230mL of water, and then again with a mixture of 54g of sodium chloride and 215mL of water. After drying the washed solution with magnesium sulfate, the solvent was distilled under reduced pressure to obtain a volume of 140 g, which was then transferred to a three-necked flask and heated to 65 °C. 210 mL of methanol (manufactured by Wako Pure Chemical, Ltd.) was added dropwise between 60 and 45 °C to induce crystallization. The solution was then cooled to 0–5 °C, and the crystals were filtered off and washed with a mixture of 30 mL of ethyl acetate and 90 mL of methanol. The resulting crystals were dried under blast heat at 40 °C for 24 hours to obtain chiral reagent B (34.4 g, yield: 85%, HPLC purity: 96.9%).
[0436] Chiral reagent B 1 ¹H NMR (heavy solvent: CDCl₃): δ 8.02 (4H, d), 7.84 (2H, d), 7.50 (6H, m), 6.52 (2H, d), 5.71 (2H, s), 4.28 (4H, m), 1.35 (6H, t)
[0437] The following is a reaction diagram illustrating the synthesis method of the chiral reagent B described above.
[0438] [Chemical Formula 6]
[0439]
[0440] Furthermore, chiral reagent B can also be synthesized using the following synthetic method.
[0441] [Another method for synthesizing chiral reagent B]
[0442] Using intermediate 1, the butyl acrylate in the synthesis of intermediate 2 in Synthesis Example 1 was replaced with ethyl acrylate. Otherwise, the reaction, separation, and adsorbent treatment were performed in the same manner as the synthesis of intermediate 2. Chiral reagent B was directly synthesized by precipitating the solid using ethyl acetate / methanol and filtering it. It was confirmed that chiral reagent B could also be synthesized by the above method (Yield: 61%, HPLC purity: 99.0%).
[0443] Table 1. Chiral reagent amounts of coating solutions containing rod-shaped liquid crystal compounds [Table 1]
[0444]
[0445] <Reflective coating liquid D-1>
[0446] The following composition was stirred and dissolved in a container maintained at 50°C to prepare a coating solution D-1 for a circularly polarized light reflective layer. Here, D indicates a coating solution using a disk-shaped liquid crystal.
[0447]
[0448] Disc-shaped liquid crystal compound (A)
[0449] [Chemical Formula 7]
[0450]
[0451] Disc-shaped liquid crystal compound (B)
[0452] [Chemical Formula 8]
[0453]
[0454] Polymerizable monomer E1
[0455] [Chemical Formula 9]
[0456]
[0457] Surfactant F4
[0458] [Chemical Formula 10]
[0459]
[0460] <Reflective layer coating solutions D-2~D-5, D-11~D-16>
[0461] The amount of chiral reagent A added is changed as shown in Table 2 below. Otherwise, it is prepared in the same manner as the coating solution D-1 for the reflective layer.
[0462] Table 2. Chiral reagent amounts of coating solutions containing disc-shaped liquid crystal compounds [Table 2]
[0463]
[0464] [Fabrication of Reflective Circular Polarizer 1]
[0465] As a pseudo-support, a 50 μm thick PET (polyethylene terephthalate) film (manufactured by Toyobo Co., Ltd., A4100) was prepared. This PET film has an easy-to-adhere layer on one side.
[0466] The surface of the PET film without the easily bondable layer, as shown previously, was rubbed. After coating with the prepared reflective layer coating solution R-1 using a wire rod coater, it was dried at 110°C for 120 seconds. Subsequently, it was irradiated at 100°C with an illuminance of 80 mW / cm² under a low-oxygen atmosphere (below 100 ppm). 2 Irradiation dose 500mJ / cm 2 The light from a metal halide lamp was used to cure the liquid crystal layer, thereby forming a red light-reflecting layer (first light-reflecting layer) composed of a cholesterol-type liquid crystal layer. Light irradiation was performed entirely from the cholesterol-type liquid crystal layer side. The coating thickness was adjusted so that the cured red light-reflecting layer had a film thickness of 4.5 μm.
[0467] Next, the red light reflecting layer was subjected to a discharge rate of 150 W·min / m. 2 After corona treatment, a reflective coating solution D-1 was applied to the corona-treated surface using a wire-bar coater. The coated film was then dried at 70°C for 2 minutes to vaporize the solvent, followed by curing at 115°C for 3 minutes to achieve a uniform orientation. The coated film was then maintained at 45°C and irradiated with ultraviolet light (300 mJ / cm²) under a nitrogen atmosphere using a metal halide lamp. 2 The process involves curing the material, thereby forming a yellow light-reflecting layer (second light-reflecting layer) on top of the red light-reflecting layer. Light irradiation is performed from the cholesterol-type liquid crystal layer side. The coating thickness is then adjusted so that the cured yellow light-reflecting layer has a thickness of 3.3 μm.
[0468] Next, a reflective coating solution R-2 was applied to the yellow light-reflecting layer using a wire-bar coater, and then dried at 110°C for 120 seconds. Afterwards, the layer was irradiated at 100°C with an illuminance of 80 mW and an irradiance of 500 mJ / cm² under a low-oxygen atmosphere (below 100 ppm). 2The metal halide lamp was used to heat and cure the yellow light-reflecting layer, thereby forming a green light-reflecting layer (third light-reflecting layer) on top of the yellow light-reflecting layer. The light irradiation was performed from the cholesterol-type liquid crystal layer side. The coating thickness was adjusted so that the cured green light-reflecting layer had a thickness of 2.7 μm.
[0469] Next, the green light reflective layer was subjected to a discharge rate of 150 W·min / m. 2 After corona treatment, a light-reflecting coating solution D-2 was applied to the corona-treated surface using a wire-bar coater. The coated film was then dried at 70°C for 2 minutes to vaporize the solvent, followed by curing at 115°C for 3 minutes to achieve a uniform orientation. The coated film was then maintained at 45°C and irradiated with ultraviolet light (300 mJ / cm²) under a nitrogen atmosphere using a metal halide lamp. 2 This process solidifies the liquid crystal layer, forming a blue light-reflecting layer (fourth light-reflecting layer) on top of the green light-reflecting layer. Light irradiation is performed from the cholesterol-type liquid crystal layer side. The coating thickness is then adjusted to achieve a cured blue light-reflecting layer thickness of 2.5 μm.
[0470] [Fabrication of reflective circular polarizers 2-7 and 10-13]
[0471] Reflective circular polarizers 2-7 and 10 have their reflective layer coating liquid and film thickness modified as shown in the table below; otherwise, they are manufactured using the same method as reflective circular polarizer 1. Furthermore, reflective circular polarizers 11-13 have their number of layers increased to 6, 8, and 16 layers, respectively, and their reflective layer coating liquid and film thickness modified as shown in the table below; otherwise, they are manufactured using the same method as reflective circular polarizer 1.
[0472] Table 3-1. Coating solutions used in the fabrication of reflective circular polarizers 1 to 10
[0473] Table 3-2. Coating liquid used in the fabrication of the reflective circular polarizer 11
[0474] Table 3-3. Coating liquid used in the fabrication of the reflective circular polarizer 12
[0475] Table 3-4. Coating liquid used in the fabrication of reflective circular polarizer 13
[0476] In addition, in the table below, the coating liquid R-1 for the reflective layer is omitted and referred to as "liquid R-1".
[0477]
[0478] [Table 4]
[0479]
[0480] [Table 5]
[0481]
[0482] [Table 6]
[0483]
[0484] [The construction of reflective circular polarizer 8]
[0485] The reflective circular polarizer 8 is fabricated by transferring the light-reflecting layer of thin film 2 onto the light-reflecting layer of thin film 1, which is formed by stacking two light-reflecting layers on a dummy support. Thin film 1 is formed by sequentially forming a first light-reflecting layer and a second light-reflecting layer on the dummy support. Furthermore, thin film 2 is formed by sequentially forming a third light-reflecting layer and a fourth light-reflecting layer on the dummy support. The transfer of the light-reflecting layers is performed according to the following steps.
[0486] (1) First, the light-reflecting layer of film 2 is transferred onto the laminated film. The transfer to the laminated film is performed by attaching the laminated film with adhesive to the side opposite to the dummy support of film 2, and then peeling off the dummy support.
[0487] (2) On the side opposite to the pseudo-support of film 1, a UV adhesive chemiseal U2084B (manufactured by Chemitech Inc., refractive index n after curing: 1.60) was coated with a wire bar coater to a thickness of 2 μm. It was then laminated on the surface to make contact with the light-reflecting layer transferred onto the laminated film.
[0488] (3) In the purification chamber, after nitrogen purging until the oxygen concentration is below 100 ppm, high-pressure mercury lamp ultraviolet light is irradiated from the dummy support side of film 1 to cure it. The illuminance is 25 mW / cm². 2 The irradiation dose was 1000 mJ / cm. 2 Thus, a reflective circular polarizer 8 with a first to a fourth light-reflecting layer was obtained.
[0489] [The construction of reflective circular polarizer 9]
[0490] The spiral pitch of the second light-reflecting layer in the reflective circular polarizer 9 is continuously deformed in the thickness direction, forming a gradient pitch layer. The first and third light-reflecting layers are fabricated using the same method as the reflective circular polarizer 1. The pitch gradient layer was formed through the following steps.
[0491] After forming the first light-reflecting layer on the rubbed PET film, a reflective coating solution R-6 was applied using a wire bar coater. Next, the film was cured at 105°C for 2 minutes to obtain a uniform orientation. Subsequently, the coated film was maintained at 75°C and irradiated with ultraviolet light (30 mJ / cm²) under a low-oxygen atmosphere (below 100 ppm) using a metal halide lamp. 2 Additionally, a bandpass filter that transmits only light with wavelengths of 300 nm to 350 nm during ultraviolet irradiation was placed between the metal halide lamp and the sample. The ultraviolet irradiation dose was measured using the bandpass filter. Next, the coated film was maintained at 75°C and heat-cured for 10 seconds. Then, the coated film was maintained at 75°C and irradiated with an illuminance of 25 mW / cm² under a low-oxygen atmosphere (below 100 ppm). 2 Irradiation dose 500mJ / cm 2 The light from a metal halide lamp is used to cure the layer, thereby forming a second light-reflecting layer composed of a cholesterol-type liquid crystal layer. The light irradiation is performed from the cholesterol-type liquid crystal layer side. At this time, the coating thickness is adjusted so that the cured second light-reflecting layer has a film thickness of 7.0 μm.
[0492] The characteristics of the fabricated reflective circular polarizers 1 to 10 are shown in Table 4-1 below. Furthermore, the characteristics of the fabricated reflective circular polarizers 11 to 13 are shown in Tables 4-2, 4-3, and 4-4 below, respectively. The center wavelength of reflection (the center wavelength of the reflected light) is determined by fabricating a film with only a single layer coated. Here, the center wavelength of reflection is used to define the characteristics of a light-reflecting thin film having a reflective band using a cholesterol-type liquid crystal, referring to the midpoint of the spectral band reflected by the thin film. Specifically, it is obtained by calculating the average of the wavelengths on the short-wavelength side and the long-wavelength side relative to the half-value of peak reflectivity using the method described above. Furthermore, the SRth of the light-reflecting layers of reflective circular polarizers 1 and 4 to 11 is... i The absolute values are all below 0.25 μm. The SRth of the light-reflecting layer in reflective circular polarizers 12–13. i All absolute values were below 0.20 μm. Furthermore, the Rth value was determined using an AxoScan OPMF-1 (manufactured by Opto Science, Inc.).
[0493] Table 4-1. Fabricated Reflective Circular Polarizers 1-10 (Coating Solution, Film Thickness)
[0494] Table 4-2. Fabricated reflective circular polarizer 11 (coating solution, film thickness)
[0495] Table 4-3. Fabricated reflective circular polarizer 12 (coating solution, film thickness)
[0496] Table 4-4. Fabricated reflective circular polarizer 13 (coating solution, film thickness)
[0497]
[0498] [Table 8]
[0499]
[0500] [Table 9]
[0501]
[0502] [Table 10]
[0503]
[0504] [Fabrication of laminated optical films]
[0505] The laminated optical film was fabricated following the steps below.
[0506] <Making of C-plate 1>
[0507] Referring to the method described in paragraphs 0132 to 0134 of Japanese Patent Application Publication No. 2016-053709, the film thickness was adjusted to fabricate a positive C-plate 1. The positive C-plate 1 has Re = 0.2 nm and Rth = -310 nm.
[0508] <Fabrication of Phase Difference Layer 1>
[0509] A phase retardation layer 1 with anti-wavelength dispersion was fabricated according to the method described in paragraphs 0151 to 0163 of Japanese Patent Application Publication No. 2020-084070. The phase retardation layer 1 has Re = 146 nm and Rth = 73 nm.
[0510] <Making of C-plate 2>
[0511] The film thickness was adjusted, and otherwise, positive C-plate 2 was fabricated in the same manner as positive C-plate 1. Positive C-plate 2 has Re = 0.1 nm and Rth = -70 nm.
[0512] <Fabrication of a Linear Polarizer>
[0513] A linear polarizer was fabricated following these steps.
[0514] (Preparation of cellulose acylated film 1)
[0515] -Preparation of core layer cellulose acylate concentrate-
[0516] The following composition is added to a mixing tank and stirred to dissolve the components, thereby preparing a cellulose acetate solution for use as a core layer cellulose acylate concentrate.
[0517]
[0518] Compound F
[0519] [Chemical Formula 11]
[0520]
[0521] -Preparation of outer cellulose acylate concentrate-
[0522] A cellulose acetate solution for use as an outer layer cellulose acylate was prepared by adding 10 parts by mass of the following matting agent solution to 90 parts by mass of the above-mentioned core layer cellulose acylate concentrate.
[0523]
[0524] -Preparation of cellulose acylated film 1-
[0525] After filtering the above-mentioned core layer cellulose acylate concentrate and the above-mentioned outer layer cellulose acylate concentrate with filter paper with an average pore size of 34 μm and sintered metal filter with an average pore size of 10 μm, the above-mentioned core layer cellulose acylate concentrate and the outer layer cellulose acylate concentrate on both sides are simultaneously cast from the casting port onto a roller at 20°C (belt casting machine).
[0526] Next, the film is peeled off with a solvent content of approximately 20% by mass, and the two ends of the film in the width direction are fixed with a tenter frame clamp. The film is then dried while being stretched laterally at a stretch ratio of 1.1.
[0527] The film is then further dried by conveying it between rollers in a heat treatment apparatus to produce an optical film with a thickness of 40 μm, which is designated as cellulose acylated film 1. The resulting cellulose acylated film 1 has an in-plane retardation of 0 nm.
[0528] <Formation of Photoalignment Layer PA1>
[0529] The oriented layer forming coating solution S-PA-1 (described later) was continuously coated onto the cellulose acylated film 1 using a wire rod. The support with the coating was dried with warm air at 140°C for 120 seconds, and then the coating was irradiated with polarized ultraviolet light (10 mJ / cm²). 2 Using an ultra-high pressure mercury lamp, a photo-alignment layer PA1 was formed. The film thickness was 0.3 μm.
[0530]
[0531]
[0532] Polymer M-PA-1
[0533] [Chemical Formula 12]
[0534]
[0535] Acid-producing agent PAG-1
[0536] [Chemical Formula 13]
[0537]
[0538] Acid-producing agent CPI-110F
[0539] [Chemical Formula 14]
[0540]
[0541] <Formation of the light-absorbing anisotropic layer P1>
[0542] The following light-absorbing anisotropic layer forming coating solution SP-1 was continuously coated onto the obtained alignment layer PA1 using a wire rod. Next, the coating layer P1 was heated at 140°C for 30 seconds and then cooled to room temperature (23°C). Then, it was heated at 90°C for 60 seconds and cooled again to room temperature. Finally, an LED lamp (center wavelength 365nm) was used at an illuminance of 200mW / cm². 2 Irradiation was performed for 2 seconds under the specified irradiation conditions, thereby forming an anisotropic light-absorbing layer P1 on the alignment layer PA1. The film thickness was 1.6 μm.
[0543]
[0544] Dichroic substance D-1
[0545] [Chemical Formula 15]
[0546]
[0547] Dichroic substance D-2
[0548] [Chemical Formula 16]
[0549]
[0550] Dichroic substance D-3
[0551] [Chemical Formula 17]
[0552]
[0553] MP-1, a polymeric liquid crystal compound
[0554] [Chemical Formula 18]
[0555]
[0556] Low molecular weight liquid crystal compound M-1
[0557] [Chemical Formula 19]
[0558]
[0559] Surfactant F-1
[0560] [Chemical Formula 20]
[0561]
[0562] <Transfer of a Reflective Circular Polarizer>
[0563] The obtained reflective circular polarizer 1 was transferred onto the support side of the obtained positive C-plate 1. At this time, the transfer was performed such that the layer (the fourth light-reflecting layer) on the side opposite to the pseudo-support side of the reflective circular polarizer 1 became the positive C-plate 1 side. The pseudo-support of the reflective circular polarizer 1 was peeled off and removed after the transfer. The transfer of the reflective circular polarizer 1 was performed through the following steps.
[0564] (1) On the support side of the positive C plate 1, a UV adhesive chemiseal U2084B (manufactured by Chemitech Inc., with a refractive index n1.60 after curing) was applied to a thickness of 2 μm using a wire bar coater. It was then laminated on the plate using a laminator so that the side opposite to the pseudo support of the reflective circular polarizer 1 came into contact with the UV adhesive.
[0565] (2) In the purification chamber, after nitrogen purging until the oxygen concentration is below 100 ppm, high-pressure mercury lamp ultraviolet light is irradiated from the dummy support side of the reflective circular polarizer 1 to cure it. The illuminance is 25 mW / cm². 2 The irradiation dose was 1000 mJ / cm. 2 .
[0566] (3) Finally, the pseudo support of the reflective circular polarizer 1 was removed.
[0567] Next, a positive C-plate 2 was attached to the first light-reflecting layer side of the reflective circular polarizer 1. Then, a phase retardation layer 1 was attached to the positive C-plate 2.
[0568] Finally, the light absorption anisotropic layer P1 was transferred onto the phase retardation layer 1 using the same transfer steps as described above. However, the layers were stacked at a 45° angle between the slow axis of the phase retardation layer 1 and the absorption axis of the light absorption anisotropic layer P1, so that the polarization axis of the light emitted from the phase retardation layer 1 was parallel to the transmission axis of the light absorption anisotropic layer P1. Thus, a stacked optical film for the reflective circular polarizer 1 of Embodiment 1 was obtained.
[0569] [Evaluation of the double image]
[0570] The lens of the "Huawei VR Glass," a virtual reality display device manufactured by Huawei Technologies Co., Ltd., employing a reciprocating optical system, was disassembled, and the lens closest to the visual recognition side was removed. This lens, with a convex plano-convex lens on the visual recognition side, has a reflective circular polarizer attached to its planar side. The reflective circular polarizer was peeled off from this lens, and the linear polarizer side became the visual recognition side. The laminated optical film from Example 1 was then attached to replace the planar side. The lens with the laminated optical film was reassembled onto the main body, thus fabricating the virtual reality display device. In the fabricated virtual reality display device, a black and white checkered pattern was displayed on the image display panel. The visual recognition of ghosting was evaluated in three stages by visual observation.
[0571] A; completely invisible
[0572] B; Although it seems like a small amount, I don't care.
[0573] C; Clearly visible
[0574] Furthermore, the laminated optical films of Examples 2-11 and Comparative Example 1 were fabricated using the same steps, and the visual recognition of ghosting was evaluated. The types of reflective circular polarizers used in each example and comparative example are shown in Table 5. The evaluation results are shown in Table 6.
[0575] As a result, in the virtual reality display devices of Examples 1 to 11, the entire area covering the lens is at a level that is completely invisible or inconspicuous. On the other hand, in the virtual reality display device of Comparative Example 1, in the black display area of the black and white checkered pattern, the light of a portion of the white display area is clearly visually recognized as a ghost image.
[0576] Furthermore, as a more sensitive method for evaluating ghosting, in the virtual reality display device that was manufactured, a black and white grid pattern was displayed on the image display panel, and the visual recognition of ghosting (the image) was evaluated in two stages using a camera image based on a luminance meter (IC-PMI16, an imaging color luminance meter with an AR / VR lens for head-mounted display evaluation manufactured by Radiant Vision Systems).
[0577] A; completely invisible
[0578] B; visible
[0579] As a result, in the virtual reality display devices of Examples 9-11, the ghosting visual recognition (camera image) covers the entire area of the lens and is completely invisible. On the other hand, in the virtual reality display devices of Comparative Example 1 and Examples 1-8, in the black display area of the black and white grid pattern, the light of a part of the white display area is identified as ghosting in the camera image.
[0580] Table 5. Types of reflective circular polarizers used in the examples and comparative examples
[0581] [Table 11]
[0582]
[0583] Table 6. Evaluation Results of Ghosting
[0584] [Table 12]
[0585]
[0586] [Examples 12-15]
[0587] In the step of obtaining the stacked optical film used in Example 1, the positive C plate 1 was not stacked. Otherwise, the stacked optical film used in Example 12 was obtained in the same manner as in Example 1.
[0588] Furthermore, in the step of obtaining the stacked optical film used in Examples 9 to 11, the positive C plate 1 was not stacked. Otherwise, the stacked optical film used in Examples 13 to 15 was obtained in the same manner as in Examples 9 to 11.
[0589] For the stacked optical films used in Examples 12-15, ghosting was evaluated in the same manner as in the above examples. The results showed that the evaluation of ghosting visual recognition and ghosting visual recognition (camera image) was the same as in Examples 1 and 9-11, respectively.
[0590] Symbol Explanation
[0591] 10-13 - Optical laminates; 21a, 22a, 23a - Reflective layer A; 21b, 22b, 24b - Reflective layer B; 25, 26 - Laminated reflective layers; 31 - First layer; 32 - Second layer; 33 - Third layer; 34 - Fourth layer; 27 - First layer; 28 - Second layer; 29 - Third layer; 100 - Laminated optical film; 101 - Anti-reflective layer; 102 - Positive C-plate; 103 - Reflective circular polarizer; 104 - Positive C-plate; 105 - Phase difference layer; 106 - Linear polarizer; 300 - Semi-reflective mirror; 400 - Circular polarizer; 500 - Image display panel; 1000 - Rays forming a virtual image; 2000 - Rays forming a ghost image.
Claims
1. An optical laminate having two or more stacked reflective layers, wherein, Each of the two or more stacked reflective layers includes one of the following reflective layers: Reflective layer A comprises at least one cholesterol-type liquid crystal layer formed using a first liquid crystal compound substantially composed of rod-shaped liquid crystal compounds, and does not comprise a cholesterol-type liquid crystal layer formed using a second liquid crystal compound substantially composed of disk-shaped liquid crystal compounds; and Reflective layer B comprises at least one cholesterol-type liquid crystal layer formed using the second liquid crystal compound, which is substantially composed of a disk-shaped liquid crystal compound, and does not comprise a cholesterol-type liquid crystal layer formed using the first liquid crystal compound, which is substantially composed of a rod-shaped liquid crystal compound. In the stacked reflective layers of two or more layers, when two adjacent stacked reflective layers A are facing each other, the center wavelengths of the reflected light from each of the two adjacent stacked reflective layers A are different. In the stacked reflective layers of two or more layers, when two adjacent stacked reflective layers B are positioned opposite each other, the center wavelengths of the reflected light from the two adjacent stacked reflective layers B are different. The term "first liquid crystal compound substantially composed of rod-shaped liquid crystal compounds" refers to a liquid crystal compound whose content relative to the total mass of the first liquid crystal compound is 95% or more by mass. The term "second liquid crystal compound substantially composed of a disc-shaped liquid crystal compound" refers to a liquid crystal compound having a content of 95% by mass or more relative to the total mass of the second liquid crystal compound.
2. The optical laminate according to claim 1, wherein, The reflective layer A and the reflective layer B are alternately arranged in the stacking direction of the optical laminate.
3. The optical laminate according to claim 1 or 2, wherein, The total number of the stacked reflective layers is less than 20.
4. The optical laminate according to claim 1 or 2, wherein, The reflectivity of light with wavelengths of 400–700 nm is greater than 40% and less than 50%.
5. The optical laminate according to claim 1 or 2, wherein, The stacked reflective layer is formed by direct contact between one reflective layer A and one reflective layer B, or by one reflective layer A, one reflective layer B, and a sealing layer disposed between the reflective layer A and the reflective layer B.
6. A stacked optical film, comprising at least sequentially a reflective circular polarizer, a phase difference layer for converting circularly polarized light into linearly polarized light, and a linear polarizer, wherein, The reflected circular polarizer is an optical laminate as described in any one of claims 1 to 5.
7. The stacked optical film according to claim 6, wherein, The linear polarizer includes at least a light-absorbing anisotropic layer comprising a liquid crystal compound and a dichroic material.
8. The laminated optical film according to claim 6 or 7, further comprising a positive C-plate.
9. The stacked optical film according to claim 6 or 7, wherein, The surface also contains an anti-reflective layer.
10. The stacked optical film according to claim 9, wherein, The anti-reflective layer is a moth-eye film or an AR film.
11. The laminated optical film according to claim 6 or 7, comprising: Resin substrates with a tanδ peak temperature below 170℃.
12. An optical article comprising an optical laminate according to any one of claims 1 to 5.
13. A virtual reality display device comprising the optical article of claim 12.
Citation Information
Patent Citations
Inverter for induction motor
JP1987077088A
Polymeric laminate and method for correcting curling thereof
JP1989320134A
Shell separation supplying device for cassette case
JP1994259925A
Homocentric optical system
JP1995120679A
Brightness enhancement film
JP2011053705A